In vitro assay for induction of adventitious rooting on intact arabidopsis hypocotyls - Trinh, Hoang; Verstraeten, Inge; Geelen, Danny (Root Development)
Adventitious roots (AR) are de novo formed roots that emerge from any part of the plant or from callus in tissue culture, except root tissue. The plant tissue origin and the method by which they are induced determine the physiological properties of emerged ARs. Hence, a standard method encompassing all types of AR does not exist. Here we describe a method for the induction and analysis of AR that emerge from the etiolated hypocotyl of dicot plants. The hypocotyl is formed during embryogenesis and shows a determined developmental pattern which usually does not involve AR formation. However, the hypocotyl shows propensity to form de novo roots under specific circumstances such as removal of the root system, high humidity or flooding, or during de-etiolation. The hypocotyl AR emerge from a pericycle-like cell layer surrounding the vascular tissue of the central cylinder, which is reminiscent to the developmental program of lateral roots. Here we propose an easy protocol for in vitro hypocotyl AR induction from etiolated Arabidopsis seedlings.

Optimized whole mount in situ immunolocalization for Arabidopsis thaliana root meristems and lateral root primordia - Karampelias, Michael; Tejos, Ricardo; Friml, Jirí; Vanneste, Steffen (Root Development. Methods and Protocols)
Immunolocalization is a valuable tool for cell biology research that allows to rapidly determine the localization and expression levels of endogenous proteins. In plants, whole-mount in situ immunolocalization remains a challenging method, especially in tissues protected by waxy layers and complex cell wall carbohydrates. Here, we present a robust method for whole-mount in situ immunolocalization in primary root meristems and lateral root primordia in Arabidopsis thaliana. For good epitope preservation, fixation is done in an alkaline paraformaldehyde/glutaraldehyde mixture. This fixative is suitable for detecting a wide range of proteins, including integral transmembrane proteins and proteins peripherally attached to the plasma membrane. From initiation until emergence from the primary root, lateral root primordia are surrounded by several layers of differentiated tissues with a complex cell wall composition that interferes with the efficient penetration of all buffers. Therefore, immunolocalization in early lateral root primordia requires a modified method, including a strong solvent treatment for removal of hydrophobic barriers and a specific cocktail of cell wall-degrading enzymes. The presented method allows for easy, reliable, and high-quality in situ detection of the subcellular localization of endogenous proteins in primary and lateral root meristems without the need of time-consuming crosses or making translational fusions to fluorescent proteins.

Auxin methylation is required for differential growth in Arabidopsis - Abbas, Mohamad; Hernández, García J; Pollmann, Stephan; Samodelov, Sophia L; Kolb, Martina; Friml, Jirí; Hammes, Ulrich Z; Zurbriggen, Matias D; Blázquez, Miguel; Alabadí, David (PNAS)
Asymmetric auxin distribution is instrumental for the differential growth that causes organ bending on tropic stimuli and curvatures during plant development. Local differences in auxin concentrations are achieved mainly by polarized cellular distribution of PIN auxin transporters, but whether other mechanisms involving auxin homeostasis are also relevant for the formation of auxin gradients is not clear. Here we show that auxin methylation is required for asymmetric auxin distribution across the hypocotyl, particularly during its response to gravity. We found that loss-of-function mutants in Arabidopsis IAA CARBOXYL METHYLTRANSFERASE1 (IAMT1) prematurely unfold the apical hook, and that their hypocotyls are impaired in gravitropic reorientation. This defect is linked to an auxin-dependent increase in PIN gene expression, leading to an increased polar auxin transport and lack of asymmetric distribution of PIN3 in the iamt1 mutant. Gravitropic reorientation in the iamt1 mutant could be restored with either endodermis-specific expression of IAMT1 or partial inhibition of polar auxin transport, which also results in normal PIN gene expression levels. We propose that IAA methylation is necessary in gravity-sensing cells to restrict polar auxin transport within the range of auxin levels that allow for differential responses.

CLE9 peptide-induced stomatal closure is mediated by abscisic acid, hydrogen peroxide, and nitric oxide in arabidopsis thaliana - Zhang, Luosha; Shi, Xiong; Zhang, Yutao; Wang, Jiajing; Yang, Jingwei; Ishida, Takashi; Jiang, Wenqian; Han, Xiangyu; Kang, Jingke; Wang, Xuening; Pan, Lixia; Lv, Shuo; et al. (Plant Cell and Environment)
CLE peptides have been implicated in various developmental processes of plants and mediate their responses to environmental stimuli. However, the biological relevance of most CLE genes remains to be functionally characterized. Here, we report that CLE9, which is expressed in stomata, acts as an essential regulator in the induction of stomatal closure. Exogenous application of CLE9 peptides or overexpression of CLE9 effectively led to stomatal closure and enhanced drought tolerance, whereas CLE9 loss-of-function mutants were sensitivity to drought stress. CLE9-induced stomatal closure was impaired in abscisic acid (ABA)-deficient mutants, indicating that ABA is required for CLE9-medaited guard cell signalling. We further deciphered that two guard cell ABA-signalling components, OST1 and SLAC1, were responsible for CLE9-induced stomatal closure. MPK3 and MPK6 were activated by the CLE9 peptide, and CLE9 peptides failed to close stomata in mpk3 and mpk6 mutants. In addition, CLE9 peptides stimulated the induction of hydrogen peroxide (H2O2) and nitric oxide (NO) synthesis associated with stomatal closure, which was abolished in the NADPH oxidase-deficient mutants or nitric reductase mutants, respectively. Collectively, our results reveal a novel ABA-dependent function of CLE9 in the regulation of stomatal apertures, thereby suggesting a potential role of CLE9 in the stress acclimatization of plants.

Gibberellin DELLA signaling targets the retromer complex to redirect protein trafficking to the plasma membrane - Salanenka, Yuliya; Verstraeten, Inge; Löfke, Christian; Tabata, Kaori; Naramoto, Satoshi; Glanc, Matous; Friml, Jirí (PNAS)
The plant hormone gibberellic acid (GA) is a crucial regulator of growth and development. The main paradigm of GA signaling puts forward transcriptional regulation via the degradation of DELLA transcriptional repressors. GA has also been shown to regulate tropic responses by modulation of the plasma membrane incidence of PIN auxin transporters by an unclear mechanism. Here we uncovered the cellular and molecular mechanisms by which GA redirects protein trafficking and thus regulates cell surface functionality. Photoconvertible reporters revealed that GA balances the protein traffic between the vacuole degradation route and recycling back to the cell surface. Low GA levels promote vacuolar delivery and degradation of multiple cargos, including PIN proteins, whereas high GA levels promote their recycling to the plasma membrane. This GA effect requires components of the retromer complex, such as Sorting Nexin 1 (SNX1) and its interacting, microtubule (MT)-associated protein, the Cytoplasmic Linker-Associated Protein (CLASP1). Accordingly, GA regulates the subcellular distribution of SNX1 and CLASP1, and the intact MT cytoskeleton is essential for the GA effect on trafficking. This GA cellular action occurs through DELLA proteins that regulate the MT and retromer presumably via their interaction partners Prefoldins (PFDs). Our study identified a branching of the GA signaling pathway at the level of DELLA proteins, which, in parallel to regulating transcription, also target by a nontranscriptional mechanism the retromer complex acting at the intersection of the degradation and recycling trafficking routes. By this mechanism, GA can redirect receptors and transporters to the cell surface, thus coregulating multiple processes, including PIN-dependent auxin fluxes during tropic responses.

KIRA1 and ORESARA1 terminate flower receptivity by promoting cell death in the stigma of Arabidopsis - Gao, Zhen; Daneva, Anna; Salanenka, Yuliya; Van Durme, Matthias; Huysmans, Marlies; Lin, Zongcheng; De Winter, Freya; Vanneste, Steffen; Karimi, Mansour; Van De Velde, Jan; Vandepoele, Klaas; Van De Walle, Davy; et al. (Nature Plants)
Flowers have a species-specific functional life span that determines the time window in which pollination, fertilization and seed set can occur. The stigma tissue plays a key role in flower receptivity by intercepting pollen and initiating pollen tube growth toward the ovary. In this article, we show that a developmentally controlled cell death programme terminates the functional life span of stigma cells in Arabidopsis. We identified the leaf senescence regulator ORESARA1 (also known as ANAC092) and the previously uncharacterized KIRA1 (also known as ANAC074) as partially redundant transcription factors that modulate stigma longevity by controlling the expression of programmed cell death-associated genes. KIRA1 expression is sufficient to induce cell death and terminate floral receptivity, whereas lack of both KIRA1 and ORESARA1 substantially increases stigma life span. Surprisingly, the extension of stigma longevity is accompanied by only a moderate extension of flower receptivity, suggesting that additional processes participate in the control of the flower's receptive life span.

Maternal auxin supply contributes to early embryo patterning in Arabidopsis - Robert, Hélène; Park, Chulmin; Gutièrrez, Carla; Wójcikowska, Barbara; Pěnčík, Aleš; Novák, Ondřej; Chen, Junyi; Grunewald, Wim; Dresselhaus, Thomas; Friml, Jirí; Laux, Thomas (Nature Plants)
The angiosperm seed is composed of three genetically distinct tissues: the diploid embryo that originates from the fertilized egg cell, the triploid endosperm that is produced from the fertilized central cell, and the maternal sporophytic integuments that develop into the seed coat1. At the onset of embryo development in Arabidopsis thaliana, the zygote divides asymmetrically, producing a small apical embryonic cell and a larger basal cell that connects the embryo to the maternal tissue2. The coordinated and synchronous development of the embryo and the surrounding integuments, and the alignment of their growth axes, suggest communication between maternal tissues and the embryo. In contrast to animals, however, where a network of maternal factors that direct embryo patterning have been identified3,4, only a few maternal mutations have been described to affect embryo development in plants5–7. Early embryo patterning in Arabidopsis requires accumulation of the phytohormone auxin in the apical cell by directed transport from the suspensor8–10. However, the origin of this auxin has remained obscure. Here we investigate the source of auxin for early embryogenesis and provide evidence that the mother plant coordinates seed development by supplying auxin to the early embryo from the integuments of the ovule. We show that auxin response increases in ovules after fertilization, due to upregulated auxin biosynthesis in the integuments, and this maternally produced auxin is required for correct embryo development.

NHX antiporters regulate the pH of endoplasmic reticulum and auxin-mediated development - Fan, Ligang; Zhao, Lei; Hu, Wei; Li, Weina; Novák, Ondřej; Strnad, Miroslav; Simon, Sibu; Friml, Jirí; Shen, Jinbo; Jiang, Liwen; Qiu, Quan (Plant, Cell and Environment)
AtNHX5 and AtNHX6 are endosomal Na+,K+/H+ antiporters that are critical for growth and development in Arabidopsis, but the mechanism behind their action remains unknown. Here, we report that AtNHX5 and AtNHX6, functioning as H+ leak, control auxin homeostasis and auxin-mediated development. We found that nhx5 nhx6 exhibited growth variations of auxin-related defects. We further showed that nhx5 nhx6 was affected in auxin homeostasis. Genetic analysis showed that AtNHX5 and AtNHX6 were required for the function of the ER-localized auxin transporter PIN5. Although AtNHX5 and AtNHX6 were co-localized with PIN5 at ER, they did not interact directly. Instead, the conserved acidic residues in AtNHX5 and AtNHX6, which are essential for exchange activity, were required for PIN5 function. AtNHX5 and AtNHX6 regulated the pH in ER. Overall, AtNHX5 and AtNHX6 may regulate auxin transport across the ER via the pH gradient created by their transport activity. H+-leak pathway provides a fine-tuning mechanism that controls cellular auxin fluxes.

Rapid and reversible root growth inhibition by TIR1 auxin signalling - Fendrych, Matyas; Akhmanova, Maria; Merrin, Jack; Glanc, Matous; Hagihara, Shinya; Takahashi, Koji; Uchida, Naoyuki; Torii, Keiko U; Friml, Jirí (Nature Plants)
The phytohormone auxin is the information carrier in a plethora of developmental and physiological processes in plants(1). It has been firmly established that canonical, nuclear auxin signalling acts through regulation of gene transcription(2). Here, we combined microfluidics, live imaging, genetic engineering and computational modelling to reanalyse the classical case of root growth inhibition(3) by auxin. We show that Arabidopsis roots react to addition and removal of auxin by extremely rapid adaptation of growth rate. This process requires intracellular auxin perception but not transcriptional reprogramming. The formation of the canonical TIR1/AFB-Aux/IAA co-receptor complex is required for the growth regulation, hinting to a novel, non-transcriptional branch of this signalling pathway. Our results challenge the current understanding of root growth regulation by auxin and suggest another, presumably non-transcriptional, signalling output of the canonical auxin pathway.

Relative contribution of PIN-containing secretory vesicles and plasma membrane PINs to the directed auxin transport: Theoretical estimation - Hille, Sander; Akhmanova, Maria; Glanc, Matous; Johnson, Alexander J; Friml, Jirí (International Journal of Molecular Sciences)
The intercellular transport of auxin is driven by PIN-formed (PIN) auxin efflux carriers. PINs are localized at the plasma membrane (PM) and on constitutively recycling endomembrane vesicles. Therefore, PINs can mediate auxin transport either by direct translocation across the PM or by pumping auxin into secretory vesicles (SVs), leading to its secretory release upon fusion with the PM. Which of these two mechanisms dominates is a matter of debate. Here, we addressed the issue with a mathematical modeling approach. We demonstrate that the efficiency of secretory transport depends on SV size, half-life of PINs on the PM, pH, exocytosis frequency and PIN density. 3D structured illumination microscopy (SIM) was used to determine PIN density on the PM. Combining this data with published values of the other parameters, we show that the transport activity of PINs in SVs would have to be at least 1000× greater than on the PM in order to produce a comparable macroscopic auxin transport. If both transport mechanisms operated simultaneously and PINs were equally active on SVs and PM, the contribution of secretion to the total auxin flux would be negligible. In conclusion, while secretory vesicle-mediated transport of auxin is an intriguing and theoretically possible model, it is unlikely to be a major mechanism of auxin transport inplanta.

Temperature-induced changes in the wheat phosphoproteome reveal temperature-regulated interconversion of phosphoforms - Vu, Lam; Zhu, Tingting; Verstraeten, Inge; Van De Cotte, Brigitte; Gevaert, Kris; De Smet, Ive (Journal of Experimental Botany)
Wheat (Triticum ssp.) is one of the most important human food sources. However, this crop is very sensitive to temperature changes. Specifically, processes during wheat leaf, flower, and seed development and photosynthesis, which all contribute to the yield of this crop, are affected by high temperature. While this has to some extent been investigated on physiological, developmental, and molecular levels, very little is known about early signalling events associated with an increase in temperature. Phosphorylation-mediated signalling mechanisms, which are quick and dynamic, are associated with plant growth and development, also under abiotic stress conditions. Therefore, we probed the impact of a short-term and mild increase in temperature on the wheat leaf and spikelet phosphoproteome. In total, 3822 (containing 5178 phosphosites) and 5581 phosphopeptides (containing 7023 phosphosites) were identified in leaf and spikelet samples, respectively. Following statistical analysis, the resulting data set provides the scientific community with a first large-scale plant phosphoproteome under the control of higher ambient temperature. This community resource on the high temperature-mediated wheat phosphoproteome will be valuable for future studies. Our analyses also revealed a core set of common proteins between leaf and spikelet, suggesting some level of conserved regulatory mechanisms. Furthermore, we observed temperature-regulated interconversion of phosphoforms, which probably impacts protein activity.

The Chara genome: Secondary complexity and implications for plant terrestrialization - Nishiyama, Tomoaki; Sakayama, Hidetoshi; De Vries, Jan; Buschmann, Henrik; Saint Marcoux, Denis; Ullrich, Kristian; Haas, Fabian; Vanderstraeten, Lisa; Becker, Dirk; Lang, Daniel; Vosolsobě, Stanislav; Rombauts, Stephane; et al. (Cell)
Land plants evolved from charophytic algae, among which Charophyceae possess the most complex body plans. We present the genome of Chara braunii; comparison of the genome to those of land plants identified evolutionary novelties for plant terrestrialization and land plant heritage genes. C. braunii employs unique xylan synthases for cell wall biosynthesis, a phragmoplast (cell separation) mechanism similar to that of land plants, and many phytohormones. C. braunii plastids are controlled via land-plant-like retrograde signaling, and transcriptional regulation is more elaborate than in other algae. The morphological complexity of this organism may result from expanded gene families, with three cases of particular note: genes effecting tolerance to reactive oxygen species (ROS), LysM receptor-like kinases, and transcription factors (TFs). Transcriptomic analysis of sexual reproductive structures reveals intricate control by TFs, activity of the ROS gene network, and the ancestral use of plant-like storage and stress protection proteins in the zygote.

The inhibitor Endosidin 4 targets SEC7 domain-type ARF GTPase exchange factors and interferes with sub cellular trafficking in eukaryotes - Kania, Urszula; Nodzyński, Tomasz; Lu, Qing; Hicks, Glenn R; Nerinckx, Wim; Mishev, Kiril; Peurois, Francois; Cherfils, Jacqueline; De, Rycke Riet Maria; Grones, Peter; Robert, Stéphanie; Russinova, Eugenia; et al. (The Plant Cell)
The trafficking of subcellular cargos in eukaryotic cells crucially depends on vesicle budding, a process mediated by ARF-GEFs (ADP-ribosylation factor guanine nucleotide exchange factors). In plants, ARF-GEFs play essential roles in endocytosis, vacuolar trafficking, recycling, secretion, and polar trafficking. Moreover, they are important for plant development, mainly through controlling the polar subcellular localization of PIN-FORMED (PIN) transporters of the plant hormone auxin. Here, using a chemical genetics screen in Arabidopsis thaliana, we identified Endosidin 4 (ES4), an inhibitor of eukaryotic ARF-GEFs. ES4 acts similarly to and synergistically with the established ARF-GEF inhibitor Brefeldin A and has broad effects on intracellular trafficking, including endocytosis, exocytosis, and vacuolar targeting. Additionally, Arabidopsis and yeast (Sacharomyces cerevisiae) mutants defective in ARF-GEF show altered sensitivity to ES4. ES4 interferes with the activation-based membrane association of the ARF1 GTPases, but not of their mutant variants that are activated independently of ARF-GEF activity. Biochemical approaches and docking simulations confirmed that ES4 specifically targets the SEC7 domain-containing ARF-GEFs. These observations collectively identify ES4 as a chemical tool enabling the study of ARF-GEF-mediated processes, including ARF-GEF-mediated plant development.

The dynamics of root cap sloughing in Arabidopsis is regulated by peptide signalling - Shi, Chun Lin; Von Wangenheim, Daniel; Herrmann, Ullrich; Wildhagen, Mari; Kulik, Ivan; Kopf, Andreas; Ishida, Takashi; Olsson, Vilde; Anker, Mari Kristine; Albert, Markus; Butenko, Melinka A; Felix, Georg; et al. (Nature Plants)
The root cap protects the stem cell niche of angiosperm roots from damage. In Arabidopsis, lateral root cap (LRC) cells covering the meristematic zone are regularly lost through programmed cell death, while the outermost layer of the root cap covering the tip is repeatedly sloughed. Efficient coordination with stem cells producing new layers is needed to maintain a constant size of the cap. We present a signalling pair, the peptide IDA-LIKE1 (IDL1) and its receptor HAESA-LIKE2 (HSL2), mediating such communication. Live imaging over several days characterized this process from initial fractures in LRC cell files to full separation of a layer. Enhanced expression of IDL1 in the separating root cap layers resulted in increased frequency of sloughing, balanced with generation of new layers in a HSL2-dependent manner. Transcriptome analyses linked IDL1-HSL2 signalling to the transcription factors BEARSKIN1/2 and genes associated with programmed cell death. Mutations in either IDL1 or HSL2 slowed down cell division, maturation and separation. Thus, IDL1-HSL2 signalling potentiates dynamic regulation of the homeostatic balance between stem cell division and sloughing activity.

Molecular evolution and diversification of the SMXL gene family - Moturu, Taraka Ramji; Thula, Sravankumar; Singh, Ravi Kumar; Nodzyński, Tomasz; Vařeková, Radka Svobodová; Friml, Jiří; Simon, Sibu (Journal of Experimental Botany)
Strigolactones (SLs) are a relatively recent addition to the list of plant hormones that control different aspects of plant development. SL signalling is perceived by an α/β hydrolase, DWARF 14 (D14). A close homolog of D14, KARRIKIN INSENSTIVE2 (KAI2), is involved in perception of an uncharacterized molecule called karrikin (KAR). Recent studies in Arabidopsis identified the SUPPRESSOR OF MAX2 1 (SMAX1) and SMAX1-LIKE 7 (SMXL7) to be potential SCF–MAX2 complex-mediated proteasome targets of KAI2 and D14, respectively. Genetic studies on SMXL7 and SMAX1 demonstrated distinct developmental roles for each, but very little is known about these repressors in terms of their sequence features. In this study, we performed an extensive comparative analysis of SMXLs and determined their phylogenetic and evolutionary history in the plant lineage. Our results show that SMXL family members can be sub-divided into four distinct phylogenetic clades/classes, with an ancient SMAX1. Further, we identified the clade-specific motifs that have evolved and that might act as determinants of SL-KAR signalling specificity. These specificities resulted from functional diversities among the clades. Our results suggest that a gradual co-evolution of SMXL members with their upstream receptors D14/KAI2 provided an increased specificity to both the SL perception and response in land plants.
Keywords: Plant Science; Physiology

PATELLINS are regulators of auxin mediated PIN1 relocation and plant development in Arabidopsis thaliana - Tejos, Ricardo; Rodríguez Furlán, Cecilia; Adamowski, Maciek; Sauer, Michael; Norambuena, Lorena; Friml, Jirí (Journal of Cell Science)
Coordinated cell polarization in developing tissues is a recurrent theme in multicellular organisms. In plants, a directional distribution of the plant hormone auxin is at the core of many developmental programs. A feedback regulation of auxin on the polarized localization of PIN auxin transporters in individual cells has been proposed as a self-organizing mechanism for coordinated tissue polarization, but the molecular mechanisms linking auxin signalling to PIN-dependent auxin transport remain unknown. We performed a microarray-based approach to find regulators of the auxin-induced PIN relocation in the Arabidopsis thaliana root. We identified a subset of a family of phosphatidylinositol transfer proteins (PITP), the PATELLINs (PATL). Here, we show that PATLs are expressed in partially overlapping cells types in different tissues going through mitosis or initiating differentiation programs. PATLs are plasma membrane-associated proteins accumulated in Arabidopsis embryos, primary roots, lateral root primordia, and developing stomata. Higher order patl mutants display reduced PIN1 repolarization in response to auxin, shorter root apical meristem, and drastic defects in embryo and seedling development. This suggests PATLs redundantly play a crucial role in polarity and patterning in Arabidopsis.

Mechanistic framework for cell-intrinsic re-establishment of PIN2 polarity after cell division - Glanc, Matous; Fendrych, Matyas; Friml, Jirí (Nature Plants)
Cell polarity, manifested by the localization of proteins to distinct polar plasma membrane domains, is a key prerequisite of multicellular life. In plants, PIN auxin transporters are prominent polarity markers crucial for a plethora of developmental processes. Cell polarity mechanisms in plants are distinct from other eukaryotes and still largely elusive. In particular, how the cell polarities are propagated and maintained following cell division remains unknown. Plant cytokinesis is orchestrated by the cell plate—a transient centrifugally growing endomembrane compartment ultimately forming the cross wall1. Trafficking of polar membrane proteins is typically redirected to the cell plate, and these will consequently have opposite polarity in at least one of the daughter cells2–5. Here, we provide mechanistic insights into post-cytokinetic re-establishment of cell polarity as manifested by the apical, polar localization of PIN2. We show that the apical domain is defined in a cell-intrinsic manner and that re-establishment of PIN2 localization to this domain requires de novo protein secretion and endocytosis, but not basal-to-apical transcytosis. Furthermore, we identify a PINOID-related kinase WAG1, which phosphorylates PIN2 in vitro6 and is transcriptionally upregulated specifically in dividing cells, as a crucial regulator of post-cytokinetic PIN2 polarity re-establishment.

A functional study of AUXILIN LIKE1 and 2 two putative clathrin uncoating factors in Arabidopsis - Adamowski, Maciek; Narasimhan, Madhumitha; Kania, Urszula; Glanc, Matous; De Jaeger, Geert; Friml, Jirí (The Plant Cell)
Clathrin-mediated endocytosis (CME) is a cellular trafficking process in which cargoes and lipids are internalized from the plasma membrane into vesicles coated with clathrin and adaptor proteins. CME is essential for many developmental and physiological processes in plants, but its underlying mechanism is not well characterised compared to that in yeast and animal systems. Here, we searched for new factors involved in CME in Arabidopsis thaliana by performing Tandem Affinity Purification of proteins that interact with clathrin light chain, a principal component of the clathrin coat. Among the confirmed interactors, we found two putative homologues of the clathrin-coat uncoating factor auxilin previously described in non-plant systems. Overexpression of AUXILIN-LIKE1 and AUXILIN-LIKE2 in A. thaliana caused an arrest of seedling growth and development. This was concomitant with inhibited endocytosis due to blocking of clathrin recruitment after the initial step of adaptor protein binding to the plasma membrane. By contrast, auxilin-like(1/2) loss-of-function lines did not present endocytosis-related developmental or cellular phenotypes under normal growth conditions. This work contributes to the on-going characterization of the endocytotic machinery in plants and provides a robust tool for conditionally and specifically interfering with CME in A. thaliana.

WRKY23 is a component of the transcriptional network mediating auxin feedback on PIN polarity - Prat, Tomas; Hajny, Jakub; Grunewald, Wim; Vasileva, Mina K; Molnar, Gergely; Tejos, Ricardo; Schmid, Markus; Sauer, Michael; Friml, Jirí (PLoS Genetics)
Auxin is unique among plant hormones due to its directional transport that is mediated by the polarly distributed PIN auxin transporters at the plasma membrane. The canalization hypothesis proposes that the auxin feedback on its polar flow is a crucial, plant-specific mechanism mediating multiple self-organizing developmental processes. Here, we used the auxin effect on the PIN polar localization in Arabidopsis thaliana roots as a proxy for the auxin feedback on the PIN polarity during canalization. We performed microarray experiments to find regulators of this process that act downstream of auxin. We identified genes that were transcriptionally regulated by auxin in an AXR3/IAA17- and ARF7/ARF19-dependent manner. Besides the known components of the PIN polarity, such as PID and PIP5K kinases, a number of potential new regulators were detected, among which the WRKY23 transcription factor, which was characterized in more detail. Gain- and loss-of-function mutants confirmed a role for WRKY23 in mediating the auxin effect on the PIN polarity. Accordingly, processes requiring auxin-mediated PIN polarity rearrangements, such as vascular tissue development during leaf venation, showed a higher WRKY23 expression and required the WRKY23 activity. Our results provide initial insights into the auxin transcriptional network acting upstream of PIN polarization and, potentially, canalization-mediated plant development.

PID/WAG-mediated phosphorylation of the Arabidopsis PIN3 auxin transporter mediates polarity switches during gravitropism - Grones, Peter; Abas, Melinda F; Hajny, Jakub; Jones, Angharad; Waidmann, Sascha; Kleine Vehn, Jürgen; Friml, Jirí (Scientific Reports)
Intercellular distribution of the plant hormone auxin largely depends on the polar subcellular distribution of the plasma membrane PIN-FORMED (PIN) auxin transporters. PIN polarity switches in response to different developmental and environmental signals have been shown to redirect auxin fluxes mediating certain developmental responses. PIN phosphorylation at different sites and by different kinases is crucial for PIN function. Here we investigate the role of PIN phosphorylation during gravitropic response. Loss- and gain-of-function mutants in PINOID and related kinases but not in D6PK kinase as well as mutations mimicking constitutive dephosphorylated or phosphorylated status of two clusters of predicted phosphorylation sites partially disrupted PIN3 phosphorylation and caused defects in gravitropic bending in roots and hypocotyls. In particular, they impacted PIN3 polarity rearrangements in response to gravity and during feed-back regulation by auxin itself. Thus PIN phosphorylation, besides regulating transport activity and apical-basal targeting, is also important for the rapid polarity switches in response to environmental and endogenous signals.

Real-time analysis of auxin response, cell wall pH and elongation in Arabidopsis thaliana Hypocotyls - Li, Lanxin; Krens, Gabriel; Fendrych, Matyas; Friml, Jirí (Bio-protocol)
The rapid auxin-triggered growth of the Arabidopsis hypocotyls involves the nuclear TIR1/AFB-Aux/IAA signaling and is accompanied by acidification of the apoplast and cell walls (Fendrych et al., 2016). Here, we describe in detail the method for analysis of the elongation and the TIR1/AFB-Aux/IAA-dependent auxin response in hypocotyl segments as well as the determination of relative values of the cell wall pH.

Control of endogenous auxin levels in plant root development - Olatunji, Damilola; Geelen, Danny; Verstraeten, Inge (International Journal of Molecular Sciences)
In this review, we summarize the different biosynthesis-related pathways that contribute to the regulation of endogenous auxin in plants. We demonstrate that all known genes involved in auxin biosynthesis also have a role in root formation, from the initiation of a root meristem during embryogenesis to the generation of a functional root system with a primary root, secondary lateral root branches and adventitious roots. Furthermore, the versatile adaptation of root development in response to environmental challenges is mediated by both local and distant control of auxin biosynthesis. In conclusion, auxin homeostasis mediated by spatial and temporal regulation of auxin biosynthesis plays a central role in determining root architecture.

Auxin response cell autonomously controls ground tissue initiation in the early arabidopsis embryo - Möller, Barbara; Ten Hove, Colette; Xiang, Daoquan; Williams, Nerys; López, Lorena; Yoshida, Saiko; Smit, Margot; Datla, Raju; Weijers, Dolf (PNAS)
Plant organs are typically organized into three main tissue layers. The middle ground tissue layer comprises the majority of the plant body and serves a wide range of functions, including photosynthesis, selective nutrient uptake and storage, and gravity sensing. Ground tissue patterning and maintenance in Arabidopsis are controlled by a well-established gene network revolving around the key regulator SHORT-ROOT (SHR). In contrast, it is completely unknown how ground tissue identity is first specified from totipotent precursor cells in the embryo. The plant signaling molecule auxin, acting through AUXIN RESPONSE FACTOR (ARF) transcription factors, is critical for embryo patterning. The auxin effector ARF5/MONOPTEROS (MP) acts both cell-autonomously and noncell-autonomously to control embryonic vascular tissue formation and root initiation, respectively. Here we show that auxin response and ARF activity cell-autonomously control the asymmetric division of the first ground tissue cells. By identifying embryonic target genes, we show that MP transcriptionally initiates the ground tissue lineage and acts upstream of the regulatory network that controls ground tissue patterning and maintenance. Strikingly, whereas the SHR network depends on MP, this MP function is, at least in part, SHR independent. Our study therefore identifies auxin response as a regulator of ground tissue specification in the embryonic root, and reveals that ground tissue initiation and maintenance use different regulators and mechanisms. Moreover, our data provide a framework for the simultaneous formation of multiple cell types by the same transcriptional regulator.

EXO70C2 is a key regulatory factor for optimal tip growth of pollen - Synek, Lukáš; Vukašinović, Nemanja; Kulich, Ivan; Hála, Michal; Aldorfová, Klára; Fendrych, Matyas; Žárský, Viktor (Plant Physiology)
The exocyst, a eukaryotic tethering complex, coregulates targeted exocytosis as an effector of small GTPases in polarized cell growth. In land plants, several exocyst subunits are encoded by double or triple paralogs, culminating in tens of EXO70 paralogs. Out of 23 Arabidopsis thaliana EXO70 isoforms, we analyzed seven isoforms expressed in pollen. Genetic and microscopic analyses of single mutants in EXO70A2, EXO70C1, EXO70C2, EXO70F1, EXO70H3, EXO70H5, and EXO70H6 genes revealed that only a loss-of-function EXO70C2 allele resulted in a significant male-specific transmission defect (segregation 40%:51%:9%) due to aberrant pollen tube growth. Mutant pollen tubes grown in vitro exhibited an enhanced growth rate and a decreased thickness of the tip cell wall, causing tip bursts. However, exo70C2 pollen tubes could frequently recover and restart their speedy elongation, resulting in a repetitive stop-and-go growth dynamics. A pollenspecific depletion of the closest paralog, EXO70C1, using artificial microRNA in the exo70C2 mutant background, resulted in a complete pollen-specific transmission defect, suggesting redundant functions of EXO70C1 and EXO70C2. Both EXO70C1 and EXO70C2, GFP tagged and expressed under the control of their native promoters, localized in the cytoplasm of pollen grains, pollen tubes, and also root trichoblast cells. The expression of EXO70C2-GFP complemented the aberrant growth of exo70C2 pollen tubes. The absent EXO70C2 interactions with core exocyst subunits in the yeast two-hybrid assay, cytoplasmic localization, and genetic effect suggest an unconventional EXO70 function possibly as a regulator of exocytosis outside the exocyst complex. In conclusion, EXO70C2 is a novel factor contributing to the regulation of optimal tip growth of Arabidopsis pollen tubes.

Shaping 3D root system architecture - Morris, Emily; Griffiths, Marcus; Golebiowska, Agata; Mairhofer, Stefan; Burr Hersey, Jasmine; Goh, Tatsuaki; Von Wangenheim, Daniel; Atkinson, Brian; Sturrock, Craig; Lynch, Jonathan; Vissenberg, Kris; Ritz, Karl; et al. (Current Biology)
Plants are sessile organisms rooted in one place. The soil resources that plants require are often distributed in a highly heterogeneous pattern. To aid foraging, plants have evolved roots whose growth and development are highly responsive to soil signals. As a result, 3D root architecture is shaped by myriad environmental signals to ensure resource capture is optimised and unfavourable environments are avoided. The first signals sensed by newly germinating seeds — gravity and light — direct root growth into the soil to aid seedling establishment. Heterogeneous soil resources, such as water, nitrogen and phosphate, also act as signals that shape 3D root growth to optimise uptake. Root architecture is also modified through biotic interactions that include soil fungi and neighbouring plants. This developmental plasticity results in a ‘custom-made’ 3D root system that is best adapted to forage for resources in each soil environment that a plant colonises.

Investigations into cell polarity and trafficking in the plant model Arabidopsis thaliana - Adamowski, Maciek
The thesis encompasses several topics of plant cell biology which were studied in the model plant Arabidopsis thaliana. Chapter 1 concerns the plant hormone auxin and its polar transport through cells and tissues. The highly controlled, directional transport of auxin is facilitated by plasma membrane-localized transporters. Transporters from the PIN family direct auxin transport due to their polarized localizations at cell membranes. Substantial effort has been put into research on cellular trafficking of PIN proteins, which is thought to underlie their polar distribution. I participated in a forward genetic screen aimed at identifying novel regulators of PIN polarity. The screen yielded several genes which may be involved in PIN polarity regulation or participate in polar auxin transport by other means. Chapter 2 focuses on the endomembrane system, with particular attention to clathrin-mediated endocytosis. The project started with identification of several proteins that interact with clathrin light chains. Among them, I focused on two putative homologues of auxilin, which in non-plant systems is an endocytotic factor known for uncoating clathrin-coated vesicles in the final step of endocytosis. The body of my work consisted of an in-depth characterization of transgenic A. thaliana lines overexpressing these putative auxilins in an inducible manner. Overexpression of these proteins leads to an inhibition of endocytosis, as documented by imaging of cargoes and clathrin-related endocytic machinery. An extension of this work is an investigation into a concept of homeostatic regulation acting between distinct transport processes in the endomembrane system. With auxilin overexpressing lines, where endocytosis is blocked specifically, I made observations on the mutual relationship between two opposite trafficking processes of secretion and endocytosis. In Chapter 3, I analyze cortical microtubule arrays and their relationship to auxin signaling and polarized growth in elongating cells. In plants, microtubules are organized into arrays just below the plasma membrane, and it is thought that their function is to guide membrane-docked cellulose synthase complexes. These, in turn, influence cell wall structure and cell shape by directed deposition of cellulose fibres. In elongating cells, cortical microtubule arrays are able to reorient in relation to long cell axis, and these reorientations have been linked to cell growth and to signaling of growth-regulating factors such as auxin or light. In this chapter, I am addressing the causal relationship between microtubule array reorientation, growth, and auxin signaling. I arrive at a model where array reorientation is not guided by auxin directly, but instead is only controlled by growth, which, in turn, is regulated by auxin.

Identification of novel regulators of PIN polarity and development of novel auxin sensor - Prat, Tomas
Plant hormone auxin and its transport between cells belong to the most important mechanisms controlling plant development. Auxin itself could change localization of PINs and thereby control direction of its own flow. We performed an expression profiling experiment in Arabidopsis roots to identify potential regulators of PIN polarity which are transcriptionally regulated by auxin signalling. We identified several novel regulators and performed a detailed characterization of the transcription factor WRKY23 (At2g47260) and its role in auxin feedback on PIN polarity. Gain-of-function and dominant-negative mutants revealed that WRKY23 plays a crucial role in mediating the auxin effect on PIN polarity. In concordance, typical polar auxin transport processes such as gravitropism and leaf vascular pattern formation were disturbed by interfering with WRKY23 function. In order to identify direct targets of WRKY23, we performed consequential expression profiling experiments using a WRKY23 inducible gain-of-function line and dominant-negative WRKY23 line that is defunct in PIN re-arrangement. Among several genes mostly related to the groups of cell wall and defense process regulators, we identified LYSINE-HISTIDINE TRANSPORTER 1 (LHT1; At5g40780), a small amino acid permease gene from the amino acid/auxin permease family (AAAP), we present its detailed characterisation in auxin feedback on PIN repolarization, identified its transcriptional regulation, we propose a potential mechanism of its action. Moreover, we identified also a member of receptor-like protein kinase LRR-RLK (LEUCINE-RICH REPEAT TRANSMEMBRANE PROTEIN KINASE PROTEIN 1; LRRK1; At1g05700), which also affects auxin-dependent PIN re-arrangement. We described its transcriptional behaviour, subcellular localization. Based on global expression data, we tried to identify ligand responsible for mechanism of signalling and suggest signalling partner and interactors. Additionally, we described role of novel phytohormone group, strigolactone, in auxin-dependent PIN re-arrangement, that could be a fundament for future studies in this field. Our results provide first insights into an auxin transcriptional network targeting PIN localization and thus regulating plant development. We highlighted WRKY23 transcriptional network and characterised its mediatory role in plant development. We identified direct effectors of this network, LHT1 and LRRK1, and describe their roles in PIN re-arrangement and PIN-dependent auxin transport processes.

Cis-cinnamic acid is a novel natural auxin efflux inhibitor that promotes lateral root formation - Steenackers, Ward; Klíma, Petr; Quareshy, Mussa; Cesarino, Igor; Kumpf, Robert; Corneillie, Sander; Araújo, Pedro; Viaene, Tom; Goeminne, Geert; Nowack, Moritz; Ljung, Karin; Friml, Jirí; et al. (Plant Physiology)
Auxin steers numerous physiological processes in plants, making the tight control of its endogenous levels and spatiotemporal distribution a necessity. This regulation is achieved by different mechanisms, including auxin biosynthesis, metabolic conversions, degradation, and transport. Here, we introduce cis-cinnamic acid (c-CA) as a novel and unique addition to a small group of endogenous molecules affecting in planta auxin concentrations. c-CA is the photo-isomerization product of the phenylpropanoid pathway intermediate trans-CA (t-CA). When grown on c-CA-containing medium, an evolutionary diverse set of plant species were shown to exhibit phenotypes characteristic for high auxin levels, including inhibition of primary root growth, induction of root hairs, and promotion of adventitious and lateral rooting. By molecular docking and receptor binding assays, we showed that c-CA itself is neither an auxin nor an anti-auxin, and auxin profiling data revealed that c-CA does not significantly interfere with auxin biosynthesis. Single cell-based auxin accumulation assays showed that c-CA, and not t-CA, is a potent inhibitor of auxin efflux. Auxin signaling reporters detected changes in spatiotemporal distribution of the auxin response along the root of c-CA-treated plants, and long-distance auxin transport assays showed no inhibition of rootward auxin transport. Overall, these results suggest that the phenotypes of c-CA-treated plants are the consequence of a local change in auxin accumulation, induced by the inhibition of auxin efflux. This work reveals a novel mechanism how plants may regulate auxin levels and adds a novel, naturally occurring molecule to the chemical toolbox for the studies of auxin homeostasis.

Flavonol-induced changes in PIN2 polarity and auxin transport in the Arabidopsis thaliana rol1-2 mutant require phosphatase activity - Kuhn, Benjamin; Nodzyński, Tomasz; Errafi, Sanae; Bucher, Rahel; Gupta, Shibu; Aryal, Bibek; Dobrev, Petre; Bigler, Laurent; Geisler, Markus; Zažímalová, Eva; Friml, Jirí; Ringli, Christoph (Scientific Reports)
The phytohormone auxin is a major determinant and regulatory component important for plant development. Auxin transport between cells is mediated by a complex system of transporters such as AUX1/LAX, PIN, and ABCB proteins, and their localization and activity is thought to be influenced by phosphatases and kinases. Flavonols have been shown to alter auxin transport activity and changes in flavonol accumulation in the Arabidopsis thaliana rol1-2 mutant cause defects in auxin transport and seedling development. A new mutation in ROOTS CURL IN NPA 1 (RCN1), encoding a regulatory subunit of the phosphatase PP2A, was found to suppress the growth defects of rol1-2 without changing the flavonol content. rol1-2 rcn1-3 double mutants show wild type-like auxin transport activity while levels of free auxin are not affected by rcn1-3. In the rol1-2 mutant, PIN2 shows a flavonol-induced basal-to-apical shift in polar localization which is reversed in the rol1-2 rcn1-3 to basal localization. In vivo analysis of PINOID action, a kinase known to influence PIN protein localization in a PP2A-antagonistic manner, revealed a negative impact of flavonols on PINOID activity. Together, these data suggest that flavonols affect auxin transport by modifying the antagonistic kinase/phosphatase equilibrium.

BEN3/BIG2 ARF GEF is involved in brefeldin a-sensitive trafficking at the trans-Golgi network/early endosome in Arabidopsis thaliana - Kitakura, Saeko; Adamowski, Maciek; Matsuura, Yuki; Santuari, Luca; Kouno, Hirotaka; Arima, Kohei; Hardtke, Christian; Friml, Jirí; Kakimoto, Tatsuo; Tanaka, Hirokazu (Plant and Cell Physiology)
Membrane traffic at the trans-Golgi network (TGN) is crucial for correctly distributing various membrane proteins to their destination. Polarly localized auxin efflux proteins, including PIN-FORMED1 (PIN1), are dynamically transported between the endosomes and the plasma membrane (PM) in the plant cells. The intracellular trafficking of PIN1 protein is sensitive to a fungal toxin brefeldin A (BFA), which is known to inhibit guanine-nucleotide exchange factors for ADP ribosylation factors (ARF GEFs) such as GNOM. However, the molecular details of the BFA-sensitive trafficking pathway have not been revealed fully. In a previous study, we have identified an Arabidopsis mutant BFA-visualized endocytic trafficking defective 3 (ben3) which exhibited reduced sensitivity to BFA in terms of BFA-induced intracellular PIN1 agglomeration. Here, we show that BEN3 encodes a member of BIG family ARF GEFs, BIG2. Fluorescent proteins tagged BEN3/BIG2 co-localized with markers for TGN / early endosome (EE). Inspection of conditionally induced de novo synthesized PIN1 confirmed that its secretion to the PM is BFA-sensitive and established BEN3/BIG2 as a crucial component of this BFA action at the level of TGN/EE. Furthermore, ben3 mutation alleviated BFA-induced agglomeration of another TGN-localized ARF GEF BEN1/MIN7. Taken together our results suggest that BEN3/BIG2 is an ARF GEF component, which confers BFA sensitivity to the TGN/EE in Arabidopsis.

Vascular tissue development and regeneration in the model plant arabidopsis - Mazur, Ewa; Friml, Jirí (Plant Engineering)
Development of vascular tissue is a remarkable example of intercellular communication and coordinated development involving hormonal signaling and tissue polarity. Thus far, studies on vascular patterning and regeneration have been conducted mainly in trees—woody plants—with a well-developed layer of vascular cambium and secondary tissues. Trees are difficult to use as genetic models, i.e., due to long generation time, unstable environmental conditions, and lack of available mutants and transgenic lines. Therefore, the use of the main genetic model plant Arabidopsis thaliana (L.) Heynh., with a wealth of available marker and transgenic lines, provides a unique opportunity to address molecular mechanism of vascular tissue formation and regeneration. With specific treatments, the tiny weed Arabidopsis can serve as a model to understand the growth of mighty trees and interconnect a tree physiology with molecular genetics and cell biology of Arabidopsis.

Live tracking of moving samples in confocal microscopy for vertically grown roots - Von Wangenheim, Daniel; Hauschild, Robert; Fendrych, Matyas; Barone, Vanessa; Benková, Eva; Friml, Jirí (eLife)
Roots navigate through soil integrating environmental signals to orient their growth. The Arabidopsis root is a widely used model for developmental, physiological and cell biological studies. Live imaging greatly aids these efforts, but the horizontal sample position and continuous root tip displacement present significant difficulties. Here, we develop a confocal microscope setup for vertical sample mounting and integrated directional illumination. We present TipTracker – a custom software for automatic tracking of diverse moving objects usable on various microscope setups. Combined, this enables observation of root tips growing along the natural gravity vector over prolonged periods of time, as well as the ability to induce rapid gravity or light stimulation. We also track migrating cells in the developing zebrafish embryo, demonstrating the utility of this system in the acquisition of high-resolution data sets of dynamic samples. We provide detailed descriptions of the tools enabling the easy implementation on other microscopes.

Light sheet fluorescence microscopy of plant roots growing on the surface of a gel - Von Wangenheim, Daniel; Hauschild, Robert; Friml, Jirí (Journal of visualized experiments JoVE)
One of the key questions in understanding plant development is how single cells behave in a larger context of the tissue. Therefore, it requires the observation of the whole organ with a high spatial- as well as temporal resolution over prolonged periods of time, which may cause photo-toxic effects. This protocol shows a plant sample preparation method for light-sheet microscopy, which is characterized by mounting the plant vertically on the surface of a gel. The plant is mounted in such a way that the roots are submerged in a liquid medium while the leaves remain in the air. In order to ensure photosynthetic activity of the plant, a custom-made lighting system illuminates the leaves. To keep the roots in darkness the water surface is covered with sheets of black plastic foil. This method allows long-term imaging of plant organ development in standardized conditions.

Cellular mechanisms for cargo delivery and polarity maintenance at different polar domains in plant cells - Łangowski, Łukasz; Wabnik, Krzysztof T; Li, Hongjiang; Vanneste, Steffen; Naramoto, Satoshi; Tanaka, Hirokazu; Friml, Jirí (Cell Discovery)
The asymmetric localization of proteins in the plasma membrane domains of eukaryotic cells is a fundamental manifestation of cell polarity that is central to multicellular organization and developmental patterning. In plants, the mechanisms underlying the polar localization of cargo proteins are still largely unknown and appear to be fundamentally distinct from those operating in mammals. Here, we present a systematic, quantitative comparative analysis of the polar delivery and subcellular localization of proteins that characterize distinct polar plasma membrane domains in plant cells. The combination of microscopic analyses and computational modeling revealed a mechanistic framework common to diverse polar cargos and underlying the establishment and maintenance of apical, basal, and lateral polar domains in plant cells. This mechanism depends on the polar secretion, constitutive endocytic recycling, and restricted lateral diffusion of cargos within the plasma membrane. Moreover, our observations suggest that polar cargo distribution involves the individual protein potential to form clusters within the plasma membrane and interact with the extracellular matrix. Our observations provide insights into the shared cellular mechanisms of polar cargo delivery and polarity maintenance in plant cells.

Enquiry into the topology of plasma membrane localized PIN auxin transport components - Nodzyński, Tomasz; Vanneste, Steffen; Zwiewka, Marta; Pernisová, Markéta; Hejátko, Jan; Friml, Jirí (Molecular Plant)
Auxin directs plant ontogenesis via differential accumulation within tissues depending largely on the activity of PIN proteins that mediate auxin efflux from cells and its directional cell-to-cell transport. Regardless of the developmental importance of PINs, the structure of these transporters is poorly characterized. Here, we present experimental data concerning protein topology of plasma membrane-localized PINs. Utilizing approaches based on pH-dependent quenching of fluorescent reporters combined with immunolocalization techniques, we mapped the membrane topology of PINs and further cross-validated our results using available topology modeling software. We delineated the topology of PIN1 with two transmembrane (TM) bundles of five α-helices linked by a large intracellular loop and a C-terminus positioned outside the cytoplasm. Using constraints derived from our experimental data, we also provide an updated position of helical regions generating a verisimilitude model of PIN1. Since the canonical long PINs show a high degree of conservation in TM domains and auxin transport capacity has been demonstrated for Arabidopsis representatives of this group, this empirically enhanced topological model of PIN1 will be an important starting point for further studies on PIN structure–function relationships. In addition, we have established protocols that can be used to probe the topology of other plasma membrane proteins in plants. © 2016 The Authors

Auxin flow mediated competition between axillary buds to restore apical dominance - Balla, Jozef; Medved'Ová, Zuzana; Kalousek, Petr; Matiješčuková, Natálie; Friml, Jirí; Reinöhl, Vilém; Procházka, Stanislav (Scientific Reports)
Apical dominance is one of the fundamental developmental phenomena in plant biology, which determines the overall architecture of aerial plant parts. Here we show apex decapitation activated competition for dominance in adjacent upper and lower axillary buds. A two-nodal-bud pea (Pisum sativum L.) was used as a model system to monitor and assess auxin flow, auxin transport channels, and dormancy and initiation status of axillary buds. Auxin flow was manipulated by lateral stem wounds or chemically by auxin efflux inhibitors 2,3,5-triiodobenzoic acid (TIBA), 1-N-naphtylphtalamic acid (NPA), or protein synthesis inhibitor cycloheximide (CHX) treatments, which served to interfere with axillary bud competition. Redirecting auxin flow to different points influenced which bud formed the outgrowing and dominant shoot. The obtained results proved that competition between upper and lower axillary buds as secondary auxin sources is based on the same auxin canalization principle that operates between the shoot apex and axillary bud. © The Author(s) 2016.

A noncanonical auxin sensing mechanism is required for organ morphogenesis in arabidopsis - Simonini, Sara; Deb, Joyita; Moubayidin, Laila; Stephenson, Pauline; Valluru, Manoj; Freire Rios, Alejandra; Sorefan, Karim; Weijers, Dolf; Friml, Jirí; Östergaard, Lars (Genes and Development)
Tissue patterning in multicellular organisms is the output of precise spatio–temporal regulation of gene expression coupled with changes in hormone dynamics. In plants, the hormone auxin regulates growth and development at every stage of a plant’s life cycle. Auxin signaling occurs through binding of the auxin molecule to a TIR1/AFB F-box ubiquitin ligase, allowing interaction with Aux/IAA transcriptional repressor proteins. These are subsequently ubiquitinated and degraded via the 26S proteasome, leading to derepression of auxin response factors (ARFs). How auxin is able to elicit such a diverse range of developmental responses through a single signaling module has not yet been resolved. Here we present an alternative auxin-sensing mechanism in which the ARF ARF3/ETTIN controls gene expression through interactions with process-specific transcription factors. This noncanonical hormonesensing mechanism exhibits strong preference for the naturally occurring auxin indole 3-acetic acid (IAA) and is important for coordinating growth and patterning in diverse developmental contexts such as gynoecium morphogenesis, lateral root emergence, ovule development, and primary branch formation. Disrupting this IAA-sensing ability induces morphological aberrations with consequences for plant fitness. Therefore, our findings introduce a novel transcription factor-based mechanism of hormone perception in plants. © 2016 Simonini et al.

A model of differential growth guided apical hook formation in plants - Žádníková, Petra; Wabnik, Krzysztof T; Abuzeineh, Anas; Gallemí, Marçal; Van Der Straeten, Dominique; Smith, Richard; Inze, Dirk; Friml, Jirí; Prusinkiewicz, Przemysław; Benková, Eva (Plant Cell)
Differential cell growth enables flexible organ bending in the presence of environmental signals such as light or gravity. A prominent example of the developmental processes based on differential cell growth is the formation of the apical hook that protects the fragile shoot apical meristem when it breaks through the soil during germination. Here, we combined in silico and in vivo approaches to identify a minimal mechanism producing auxin gradient-guided differential growth during the establishment of the apical hook in the model plant Arabidopsis thaliana. Computer simulation models based on experimental data demonstrate that asymmetric expression of the PIN-FORMED auxin efflux carrier at the concave (inner) versus convex (outer) side of the hook suffices to establish an auxin maximum in the epidermis at the concave side of the apical hook. Furthermore, we propose a mechanism that translates this maximum into differential growth, and thus curvature, of the apical hook. Through a combination of experimental and in silico computational approaches, we have identified the individual contributions of differential cell elongation and proliferation to defining the apical hook and reveal the role of auxin-ethylene crosstalk in balancing these two processes. © 2016 American Society of Plant Biologists. All rights reserved.

Termination of shoot gravitropic responses by auxin feedback on PIN3 polarity - Rakusová, Hana; Abbas, Mohamad; Han, Huibin; Song, Siyuan; Robert, Hélène; Friml, Jirí (Current Biology)
Plants adjust their growth according to gravity. Gravitropism involves gravity perception, signal transduction, and asymmetric growth response, with organ bending as a consequence [1]. Asymmetric growth results from the asymmetric distribution of the plant-specific signaling molecule auxin [2] that is generated by lateral transport, mediated in the hypocotyl predominantly by the auxin transporter PIN-FORMED3 (PIN3) [3–5]. Gravity stimulation polarizes PIN3 to the bottom sides of endodermal cells, correlating with increased auxin accumulation in adjacent tissues at the lower side of the stimulated organ, where auxin induces cell elongation and, hence, organ bending. A curvature response allows the hypocotyl to resume straight growth at a defined angle [6], implying that at some point auxin symmetry is restored to prevent overbending. Here, we present initial insights into cellular and molecular mechanisms that lead to the termination of the tropic response. We identified an auxin feedback on PIN3 polarization as underlying mechanism that restores symmetry of the PIN3-dependent auxin flow. Thus, two mechanistically distinct PIN3 polarization events redirect auxin fluxes at different time points of the gravity response: first, gravity-mediated redirection of PIN3-mediated auxin flow toward the lower hypocotyl side, where auxin gradually accumulates and promotes growth, and later PIN3 polarization to the opposite cell side, depleting this auxin maximum to end the bending. Accordingly, genetic or pharmacological interference with the late PIN3 polarization prevents termination of the response and leads to hypocotyl overbending. This observation reveals a role of auxin feedback on PIN polarity in the termination of the tropic response. © 2016 Elsevier Ltd

Strong morphological defects in conditional Arabidopsis abp1 knock-down mutants generated in absence of functional ABP1 protein - Michalko, Jaroslav; Glanc, Matous; Perrot Rechenmann, Catherine; Friml, Jirí (F1000 Research)
The Auxin Binding Protein 1 (ABP1) is one of the most studied proteins in plants. Since decades ago, it has been the prime receptor candidate for the plant hormone auxin with a plethora of described functions in auxin signaling and development. The developmental importance of ABP1 has recently been questioned by identification of Arabidopsis thaliana abp1 knock-out alleles that show no obvious phenotypes under normal growth conditions. In this study, we examined the contradiction between the normal growth and development of the abp1 knock-outs and the strong morphological defects observed in three different ethanol-inducible abp1 knock-down mutants ( abp1-AS, SS12K, SS12S). By analyzing segregating populations of abp1 knock-out vs. abp1 knock-down crosses we show that the strong morphological defects that were believed to be the result of conditional down-regulation of ABP1 can be reproduced also in the absence of the functional ABP1 protein. This data suggests that the phenotypes in abp1 knock-down lines are due to the off-target effects and asks for further reflections on the biological function of ABP1 or alternative explanations for the missing phenotypic defects in the abp1 loss-of-function alleles.

Endosomal interactions during root hair growth - Von Wangenheim, Daniel; Rosero, Amparo; Komis, George; Šamajová, Olga; Ovečka, Miroslav; Voigt, Boris; Šamaj, Jozef (Frontiers in Plant Science)
The dynamic localization of endosomal compartments labeled with targeted fluorescent protein tags is routinely followed by time lapse fluorescence microscopy approaches and single particle tracking algorithms. In this way trajectories of individual endosomes can be mapped and linked to physiological processes as cell growth. However, other aspects of dynamic behavior including endosomal interactions are difficult to follow in this manner. Therefore, we characterized the localization and dynamic properties of early and late endosomes throughout the entire course of root hair formation by means of spinning disc time lapse imaging and post-acquisition automated multitracking and quantitative analysis. Our results show differential motile behavior of early and late endosomes and interactions of late endosomes that may be specified to particular root hair domains. Detailed data analysis revealed a particular transient interaction between late endosomes—termed herein as dancing-endosomes—which is not concluding to vesicular fusion. Endosomes preferentially located in the root hair tip interacted as dancing-endosomes and traveled short distances during this interaction. Finally, sizes of early and late endosomes were addressed by means of super-resolution structured illumination microscopy (SIM) to corroborate measurements on the spinning disc. This is a first study providing quantitative microscopic data on dynamic spatio-temporal interactions of endosomes during root hair tip growth.

ROTUNDA3 function in plant development by phosphatase 2A-mediated regulation of auxin transporter recycling - Karampelias, Michael; Neyt, Pia; De Groeve, Steven; Aesaert, Stijn; Coussens, Griet; Rolčík, Jakub; Bruno, Leonardo; De Winne, Nancy; Van Minnebruggen, Annemie; Van Montagu, Marc; Ponce, Maria; Micol, José; et al. (PNAS)
The shaping of organs in plants depends on the intercellular flow of the phytohormone auxin, of which the directional signaling is determined by the polar subcellular localization of PIN-FORMED (PIN) auxin transport proteins. Phosphorylation dynamics of PIN proteins are affected by the protein phosphatase 2A (PP2A) and the PINOID kinase, which act antagonistically to mediate their apical-basal polar delivery. Here, we identified the ROTUNDA3 (RON3) protein as a regulator of the PP2A phosphatase activity in Arabidopsis thaliana. The RON3 gene was map-based cloned starting from the ron3-1 leaf mutant and found to be a unique, plant-specific gene coding for a protein with high and dispersed proline content. The ron3-1 and ron3-2 mutant phenotypes [i.e., reduced apical dominance, primary root length, lateral root emergence, and growth; increased ectopic stages II, IV, and V lateral root primordia; decreased auxin maxima in indole-3-acetic acid (IAA)-treated root apical meristems; hypergravitropic root growth and response; increased IAA levels in shoot apices; and reduced auxin accumulation in root meristems] support a role for RON3 in auxin biology. The affinity-purified PP2A complex with RON3 as bait suggested that RON3 might act in PIN transporter trafficking. Indeed, pharmacological interference with vesicle trafficking processes revealed that single ron3-2 and double ron3-2 rcn1 mutants have altered PIN polarity and endocytosis in specific cells. Our data indicate that RON3 contributes to auxin-mediated development by playing a role in PIN recycling and polarity establishment through regulation of the PP2A complex activity.

TWISTED DWARF1 mediates the action of auxin transport inhibitors on actin cytoskeleton dynamics - Zhu, Jinsheng; Bailly, Aurélien; Zwiewka, Marta; Sovero, Valpuri; Di Donato, Martin; Ge, Pei; Oehri, Jacqueline; Aryal, Bibek; Hao, Pengchao; Linnert, Miriam; Burgardt, Noelia; Lücke, Christian; et al. (Plant Cell)
Plant growth and architecture is regulated by the polar distribution of the hormone auxin. Polarity and flexibility of this process is provided by constant cycling of auxin transporter vesicles along actin filaments, coordinated by a positive auxinactin feedback loop. Both polar auxin transport and vesicle cycling are inhibited by synthetic auxin transport inhibitors, such as 1-Nnaphthylphthalamic acid (NPA), counteracting the effect of auxin; however, underlying targets and mechanisms are unclear. Using NMR, we map the NPA binding surface on the Arabidopsis thaliana ABCB chaperone TWISTED DWARF1 (TWD1).We identify ACTIN7 as a relevant, although likely indirect, TWD1 interactor, and show TWD1-dependent regulation of actin filament organization and dynamics and that TWD1 is required for NPA-mediated actin cytoskeleton remodeling. The TWD1-ACTIN7 axis controls plasma membrane presence of efflux transporters, and as a consequence act7 and twd1 share developmental and physiological phenotypes indicative of defects in auxin transport. These can be phenocopied by NPA treatment or by chemical actin (de)stabilization. We provide evidence that TWD1 determines downstreamlocations of auxin efflux transporters by adjusting actin filament debundling and dynamizing processes and mediating NPA action on the latter. This function appears to be evolutionary conserved since TWD1 expression in budding yeast alters actin polarization and cell polarity and provides NPA sensitivity.

Sorting motifs involved in the trafficking and localization of the PIN1 auxin efflux carrier - Sancho Andrés, Gloria; Soriano Ortega, Esther; Gao, Caiji; Bernabé Orts, Joan; Narasimhan, Madhumitha; Müller, Anna; Tejos, Ricardo; Jiang, Liwen; Friml, Jirí; Aniento, Fernando; Marcote, Maria (Plant Physiology)
n contrast with the wealth of recent reports about the function of μ-adaptins and clathrin adaptor protein (AP) complexes, there is very little information about the motifs that determine the sorting of membrane proteins within clathrin-coated vesicles in plants. Here, we investigated putative sorting signals in the large cytosolic loop of the Arabidopsis (Arabidopsis thaliana) PIN-FORMED1 (PIN1) auxin transporter, which are involved in binding μ-adaptins and thus in PIN1 trafficking and localization. We found that Phe-165 and Tyr-280, Tyr-328, and Tyr-394 are involved in the binding of different μ-adaptins in vitro. However, only Phe-165, which binds μA(μ2)- and μD(μ3)-adaptin, was found to be essential for PIN1 trafficking and localization in vivo. The PIN1:GFP-F165A mutant showed reduced endocytosis but also localized to intracellular structures containing several layers of membranes and endoplasmic reticulum (ER) markers, suggesting that they correspond to ER or ER-derived membranes. While PIN1:GFP localized normally in a μA (μ2)-adaptin mutant, it accumulated in big intracellular structures containing LysoTracker in a μD (μ3)-adaptin mutant, consistent with previous results obtained with mutants of other subunits of the AP-3 complex. Our data suggest that Phe-165, through the binding of μA (μ2)- and μD (μ3)-adaptin, is important for PIN1 endocytosis and for PIN1 trafficking along the secretory pathway, respectively.

Danger-associated peptide signaling in Arabidopsis requires clathrin - Ortiz Morea, Fausto; Savatin, Daniel; Dejonghe, Wim; Kumar, Rahul; Luo, Yu; Adamowski, Maciek; Van Begin, Jos; Dressano, Keini; De Oliveira, Guilherme; Zhao, Xiuyang; Lu, Qing; Madder, Annemieke; et al. (PNAS)
The Arabidopsis thaliana endogenous elicitor peptides (AtPeps) are released into the apoplast after cellular damage caused by pathogens or wounding to induce innate immunity by direct binding to the membrane-localized leucine-rich repeat receptor kinases, PEP RECEPTOR1 (PEPR1) and PEPR2. Although the PEPR-mediated signaling components and responses have been studied extensively, the contributions of the subcellular localization and dynamics of the active PEPRs remain largely unknown. We used live-cell imaging of the fluorescently labeled and bioactive pep1 to visualize the intracellular behavior of the PEPRs in the Arabidopsis root meristem. We found that AtPep1 decorated the plasma membrane (PM) in a receptor-dependent manner and cointernalized with PEPRs. Trafficking of the AtPep1-PEPR1 complexes to the vacuole required neither the trans-Golgi network/early endosome (TGN/EE)-localized vacuolar H+ -ATPase activity nor the function of the brefeldin A-sensitive ADP-ribosylation factor-guanine exchange factors (ARF-GEFs). In addition, AtPep1 and different TGN/EE markers colocalized only rarely, implying that the intracellular route of this receptor-ligand pair is largely independent of the TGN/EE. Inducible overexpression of the Arabidopsis clathrin coat disassembly factor, Auxilin2, which inhibits clathrin-mediated endocytosis (CME), impaired the AtPep1-PEPR1 internalization and compromised AtPep1-mediated responses. Our results show that clathrin function at the PM is required to induce plant defense responses, likely through CME of cell surface-located signaling components.

TIR1 AFB Aux IAA auxin perception mediates rapid cell wall acidification and growth of Arabidopsis hypocotyls - Fendrych, Matyas; Leung, Jeffrey; Friml, Jirí (eLife)
Despite being composed of immobile cells, plants reorient along directional stimuli. The hormone auxin is redistributed in stimulated organs leading to differential growth and bending. Auxin application triggers rapid cell wall acidification and elongation of aerial organs of plants, but the molecular players mediating these effects are still controversial. Here we use genetically-encoded pH and auxin signaling sensors, pharmacological and genetic manipulations available for Arabidopsis etiolated hypocotyls to clarify how auxin is perceived and the downstream growth executed. We show that auxin-induced acidification occurs by local activation of H+-ATPases, which in the context of gravity response is restricted to the lower organ side. This auxin-stimulated acidification and growth require TIR1/AFB-Aux/IAA nuclear auxin perception. In addition, auxin-induced gene transcription and specifically SAUR proteins are crucial downstream mediators of this growth. Our study provides strong experimental support for the acid growth theory and clarified the contribution of the upstream auxin perception mechanisms.

Plasma membrane: Negative attraction - Molnar, Gergely; Fendrych, Matyas; Friml, Jirí (Nature Plants)
The electrostatic charge at the inner surface of the plasma membrane is strongly negative in higher organisms. A new study shows that phosphatidylinositol-4-phosphate plays a critical role in establishing plasma membrane surface charge in Arabidopsis, which regulates the correct localization of signalling components.

Cytokinins influence root gravitropism via differential regulation of auxin transporter expression and localization in Arabidopsis - Pernisová, Markéta; Prat, Tomas; Grones, Peter; Haruštiaková, Danka; Matonohova, Martina; Spíchal, Lukáš; Nodzyński, Tomasz; Friml, Jirí; Hejátko, Jan (New Phytologist)
Redirection of intercellular auxin fluxes via relocalization of the PIN-FORMED 3 (PIN3) and PIN7 auxin efflux carriers has been suggested to be necessary for the root gravitropic response. Cytokinins have also been proposed to play a role in controlling root gravitropism, but conclusive evidence is lacking. We present a detailed study of the dynamics of root bending early after gravistimulation, which revealed a delayed gravitropic response in transgenic lines with depleted endogenous cytokinins (Pro35S:AtCKX) and cytokinin signaling mutants. Pro35S:AtCKX lines, as well as a cytokinin receptor mutant ahk3, showed aberrations in the auxin response distribution in columella cells consistent with defects in the auxin transport machinery. Using in vivo real-time imaging of PIN3-GFP and PIN7-GFP in AtCKX3 overexpression and ahk3 backgrounds, we observed wild-type-like relocalization of PIN proteins in the columella early after gravistimulation, with gravity-induced relocalization of PIN7 faster than that of PIN3. Nonetheless, the cellular distribution of PIN3 and PIN7 and expression of PIN7 and the auxin influx carrier AUX1 was affected in AtCKX overexpression lines. Based on the retained cytokinin sensitivity in pin3 pin4 pin7 mutant, we propose the AUX1-mediated auxin transport rather than columella-located PIN proteins as a target of endogenous cytokinins in the control of root gravitropism.

Phosphatidylinositol 4-phosphate 5-kinases 1 and 2 are involved in the regulation of vacuole morphology during Arabidopsis thaliana pollen development - Ugalde, José; Rodríguez Furlán, Cecilia; De Rycke, Riet; Norambuena, Lorena; Friml, Jirí; León, Gabriel; Tejos, Ricardo (Plant Science)
The pollen grains arise after meiosis of pollen mother cells within the anthers. A series of complex structural changes follows, generating mature pollen grains capable of performing the double fertilization of the female megasporophyte. Several signaling molecules, including hormones and lipids, have been involved in the regulation and appropriate control of pollen development. Phosphatidylinositol 4-phophate 5-kinases (PIP5K), which catalyze the biosynthesis of the phosphoinositide PtdIns(4,5)P2, are important for tip polar growth of root hairs and pollen tubes, embryo development, vegetative plant growth, and responses to the environment. Here, we report a role of PIP5Ks during microgametogenesis. PIP5K1 and PIP5K2 are expressed during early stages of pollen development and their transcriptional activity respond to auxin in pollen grains. Early male gametophytic lethality to certain grade was observed in both pip5k1-/- and pip5k2-/- single mutants. The number of pip5k mutant alleles is directly related to the frequency of aborted pollen grains suggesting the two genes are involved in the same function. Indeed PIP5K1 and PIP5K2 are functionally redundant since homozygous double mutants did not render viable pollen grains. The loss of function of PIP5K1 and PIP5K2results in defects in vacuole morphology in pollen at the later stages and epidermal root cells. Our results show that PIP5K1, PIP5K2 and phosphoinositide signaling are important cues for early developmental stages and vacuole formation during microgametogenesis.

PIN6 auxin transporter at endoplasmic reticulum and plasma membrane mediates auxin homeostasis and organogenesis in Arabidopsis - Simon, Sibu; Skůpa, Petr; Viaene, Tom; Zwiewka, Marta; Tejos, Ricardo; Klíma, Petr; Čarná, Mária; Rolčík, Jakub; De Rycke, Riet; Moreno, Ignacio; Dobrev, Petre; Orellana, Ariel; et al. (New Phytologist)
Plant development mediated by the phytohormone auxin depends on tightly controlled cellular auxin levels at its target tissue that are largely established by intercellular and intracellular auxin transport mediated by PIN auxin transporters. Among the eight members of the Arabidopsis PIN family, PIN6 is the least characterized candidate. In this study we generated functional, fluorescent protein-tagged PIN6 proteins and performed comprehensive analysis of their subcellular localization and also performed a detailed functional characterization of PIN6 and its developmental roles. The localization study of PIN6 revealed a dual localization at the plasma membrane (PM) and endoplasmic reticulum (ER). Transport and metabolic profiling assays in cultured cells and Arabidopsis strongly suggest that PIN6 mediates both auxin transport across the PM and intracellular auxin homeostasis, including the regulation of free auxin and auxin conjugates levels. As evidenced by the loss- and gain-of-function analysis, the complex function of PIN6 in auxin transport and homeostasis is required for auxin distribution during lateral and adventitious root organogenesis and for progression of these developmental processes. These results illustrate a unique position of PIN6 within the family of PIN auxin transporters and further add complexity to the developmentally crucial process of auxin transport.

Centering the organizing center in the Arabidopsis thaliana shoot apical meristem by a combination of cytokinin signaling and self-organization - Adibi, Milad; Yoshida, Saiko; Weijers, Dolf; Fleck, Christian (PLoS One)
Plants have the ability to continously generate new organs by maintaining populations of stem cells throught their lives. The shoot apical meristem (SAM) provides a stable environment for the maintenance of stem cells. All cells inside the SAM divide, yet boundaries and patterns are maintained. Experimental evidence indicates that patterning is independent of cell lineage, thus a dynamic self-regulatory mechanism is required. A pivotal role in the organization of the SAM is played by the WUSCHEL gene (WUS). An important question in this regard is that how WUS expression is positioned in the SAM via a cell-lineage independent signaling mechanism. In this study we demonstrate via mathematical modeling that a combination of an inhibitor of the Cytokinin (CK) receptor, Arabidopsis histidine kinase 4 (AHK4) and two morphogens originating from the top cell layer, can plausibly account for the cell lineage-independent centering of WUS expression within SAM. Furthermore, our laser ablation and microsurgical experiments support the hypothesis that patterning in SAM occurs at the level of CK reception and signaling. The model suggests that the interplay between CK signaling, WUS/CLV feedback loop and boundary signals can account for positioning of the WUS expression, and provides directions for further experimental investigation.

Environmental and endogenous control of cortical microtubule orientation - Chen, Xu; Wu, Shuang; Liu, Zengyu; Friml, Jiřĺ (Trends in Cell Biology)

A forward genetic screen for new regulators of auxin mediated degradation of auxin transport proteins in Arabidopsis thaliana - Zemová, Radka; Zwiewka, Marta; Bielach, Agnieszka; Robert, Hélène; Friml, Jirí (Journal of Plant Growth Regulation)
The plant hormone auxin (indole-3-acetic acid) is a major regulator of plant growth and development including embryo and root patterning, lateral organ formation and growth responses to environmental stimuli. Auxin is directionally transported from cell to cell by the action of specific auxin influx [AUXIN-RESISTANT1 (AUX1)] and efflux [PIN-FORMED (PIN)] transport regulators, whose polar, subcellular localizations are aligned with the direction of the auxin flow. Auxin itself regulates its own transport by modulation of the expression and subcellular localization of the auxin transporters. Increased auxin levels promote the transcription of PIN2 and AUX1 genes as well as stabilize PIN proteins at the plasma membrane, whereas prolonged auxin exposure increases the turnover of PIN proteins and their degradation in the vacuole. In this study, we applied a forward genetic approach, to identify molecular components playing a role in the auxin-mediated degradation. We generated EMS-mutagenized Arabidopsis PIN2::PIN2:GFP, AUX1::AUX1:YFP eir1aux1 populations and designed a screen for mutants with persistently strong fluorescent signals of the tagged PIN2 and AUX1 after prolonged treatment with the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D). This approach yielded novel auxin degradation mutants defective in trafficking and degradation of PIN2 and AUX1 proteins and established a role for auxin-mediated degradation in plant development.

Mitochondrial uncouplers inhibit clathrin-mediated endocytosis largely through cytoplasmic acidification - Dejonghe, Wim; Kuenen, Sabine; Mylle, Evelien; Vasileva, Mina K; Keech, Olivier; Viotti, Corrado; Swerts, Jef; Fendrych, Matyas; Ortiz Morea, Fausto; Mishev, Kiril; Delang, Simon; Scholl, Stefan; et al. (Nature Communications)
ATP production requires the establishment of an electrochemical proton gradient across the inner mitochondrial membrane. Mitochondrial uncouplers dissipate this proton gradient and disrupt numerous cellular processes, including vesicular trafficking, mainly through energy depletion. Here we show that Endosidin9 (ES9), a novel mitochondrial uncoupler, is a potent inhibitor of clathrin-mediated endocytosis (CME) in different systems and that ES9 induces inhibition of CME not because of its effect on cellular ATP, but rather due to its protonophore activity that leads to cytoplasm acidification. We show that the known tyrosine kinase inhibitor tyrphostinA23, which is routinely used to block CME, displays similar properties, thus questioning its use as a specific inhibitor of cargo recognition by the AP-2 adaptor complex via tyrosine motif-based endocytosis signals. Furthermore, we show that cytoplasm acidification dramatically affects the dynamics and recruitment of clathrin and associated adaptors, and leads to reduction of phosphatidylinositol 4,5-biphosphate from the plasma membrane.

The CLE gene family in Populus trichocarpa - Liu, Zhijun; Yang, Nan; Lv, Yanting; Pan, Lixia; Lv, Shuo; Han, Huibin; Wang, Guodong (Plant Signaling & Behavior)
The CLE (CLAVATA3/Embryo Surrounding Region-related) peptides are small secreted signaling peptides that are primarily involved in the regulation of stem cell homeostasis in different plant meristems. Particularly, the characterization of the CLE41-PXY/TDR signaling pathway has greatly advanced our understanding on the potential roles of CLE peptides in vascular development and wood formation. Nevertheless, our knowledge on this gene family in a tree species is limited. In a recent study, we reported on a systematically investigation of the CLE gene family in Populus trichocarpa . The potential roles of PtCLE genes were studied by comparative analysis and transcriptional pro fi ling. Among fi fty PtCLE members, many PtCLE proteins share identical CLE motifs or contain the same CLE motif as that of AtCLEs, while PtCLE genes exhibited either comparable or distinct expression patterns comparing to their Arabidopsis counterparts. These fi ndings indicate the existence of both functional conservation and functional divergence between PtCLEs and their AtCLE orthologues. Our results provide valuable resources for future functional investigations of these critical signaling molecules in woody plants.

Vascular cambium regeneration and vessel formation in wounded inflorescence stems of Arabidopsis - Mazur, Ewa; Benková, Eva; Friml, Jirí (Scientific Reports)
Synchronized tissue polarization during regeneration or de novo vascular tissue formation is a plant-specific example of intercellular communication and coordinated development. According to the canalization hypothesis, the plant hormone auxin serves as polarizing signal that mediates directional channel formation underlying the spatio-temporal vasculature patterning. A necessary part of canalization is a positive feedback between auxin signaling and polarity of the intercellular auxin flow. The cellular and molecular mechanisms of this process are still poorly understood, not the least, because of a lack of a suitable model system. We show that the main genetic model plant, Arabidopsis (Arabidopsis thaliana) can be used to study the canalization during vascular cambium regeneration and new vasculature formation. We monitored localized auxin responses, directional auxin-transport channels formation, and establishment of new vascular cambium polarity during regenerative processes after stem wounding. The increased auxin response above and around the wound preceded the formation of PIN1 auxin transporter-marked channels from the primarily homogenous tissue and the transient, gradual changes in PIN1 localization preceded the polarity of newly formed vascular tissue. Thus, Arabidopsis is a useful model for studies of coordinated tissue polarization and vasculature formation after wounding allowing for genetic and mechanistic dissection of the canalization hypothesis.

V-ATPase activity in the TGN/EE is required for exocytosis and recycling in Arabidopsis - Yu, Luo; Scholl, Stefan; Doering, Anett; Yi, Zhang; Irani, Niloufer; Di Rubbo, Simone; Neumetzler, Lutz; Krishnamoorthy, Praveen; Van Houtte, Isabelle; Mylle, Evelien; Bischoff, Volker; Vernhettes, Samantha; et al. (Nature Plants)
In plants, vacuolar H+-ATPase (V-ATPase) activity acidifies both the trans-Golgi network/early endosome (TGN/EE) and the vacuole. This dual V-ATPase function has impeded our understanding of how the pH homeostasis within the plant TGN/EE controls exo- and endocytosis. Here, we show that the weak V-ATPase mutant deetiolated3 (det3) displayed a pH increase in the TGN/EE, but not in the vacuole, strongly impairing secretion and recycling of the brassinosteroid receptor and the cellulose synthase complexes to the plasma membrane, in contrast to mutants lacking tonoplast-localized V-ATPase activity only. The brassinosteroid insensitivity and the cellulose deficiency defects in det3 were tightly correlated with reduced Golgi and TGN/EE motility. Thus, our results provide strong evidence that acidification of the TGN/EE, but not of the vacuole, is indispensable for functional secretion and recycling in plants.

Auxin-modulated root growth inhibition in Arabidopsis thaliana seedlings with ammonium as the sole nitrogen source - Yang, Huaiyu; Von Der Fecht Bartenbach, Jenny; Friml, Jirí; Lohmann, Jan; Neuhäuser, Benjamin; Ludewig, Uwe (Functional Plant Biology)
Ammonium is the major nitrogen source in some plant ecosystems but is toxic at high concentrations, especially when available as the exclusive nitrogen source. Ammonium stress rapidly leads to various metabolic and hormonal imbalances that ultimately inhibit root and shoot growth in many plant species, including Arabidopsis thaliana (L.) Heynh. To identify molecular and genetic factors involved in seedling survival with prolonged exclusive NH4+ nutrition, a transcriptomic analysis with microarrays was used. Substantial transcriptional differences were most pronounced in (NH4)2SO4-grown seedlings, compared with plants grown on KNO3 or NH4NO3. Consistent with previous physiological analyses, major differences in the expression modules of photosynthesis-related genes, an altered mitochondrial metabolism, differential expression of the primary NH4+ assimilation, alteration of transporter gene expression and crucial changes in cell wall biosynthesis were found. A major difference in plant hormone responses, particularly of auxin but not cytokinin, was striking. The activity of the DR5::GUS reporter revealed a dramatically decreased auxin response in (NH4)2SO4-grown primary roots. The impaired root growth on (NH4)2SO4 was partially rescued by exogenous auxin or in specific mutants in the auxin pathway. The data suggest that NH4+-induced nutritional and metabolic imbalances can be partially overcome by elevated auxin levels.

Transcriptional regulation of PIN genes by FOUR LIPS and MYB88 during Arabidopsis root gravitropism - Wang, Hongzhe; Yang, Kezhen; Zou, Junjie; Zhu, Lingling; Xie, Zidian; Morita, Miyoterao; Tasaka, Masao; Friml, Jirí; Grotewold, Erich; Beeckman, Tom; Vanneste, Steffen; Sack, Fred; et al. (Nature Communications)
PIN proteins are auxin export carriers that direct intercellular auxin flow and in turn regulate many aspects of plant growth and development including responses to environmental changes. The Arabidopsis R2R3-MYB transcription factor FOUR LIPS (FLP) and its paralogue MYB88 regulate terminal divisions during stomatal development, as well as female reproductive development and stress responses. Here we show that FLP and MYB88 act redundantly but differentially in regulating the transcription of PIN3 and PIN7 in gravity-sensing cells of primary and lateral roots. On the one hand, FLP is involved in responses to gravity stimulation in primary roots, whereas on the other, FLP and MYB88 function complementarily in establishing the gravitropic set-point angles of lateral roots. Our results support a model in which FLP and MYB88 expression specifically determines the temporal-spatial patterns of PIN3 and PIN7 transcription that are closely associated with their preferential functions during root responses to gravity.

Asymmetric localizations of the ABC transporter PaPDR1 trace paths of directional strigolactone transport - Sasse, Joëlle; Simon, Sibu; Gübeli, Christian; Liu, Guowei; Cheng, Xi; Friml, Jirí; Bouwmeester, Harro; Martinoia, Enrico; Borghi, Lorenzo (Current Biology)
Strigolactones, first discovered as germination stimulants for parasitic weeds [1], are carotenoid-derived phytohormones that play major roles in inhibiting lateral bud outgrowth and promoting plant-mycorrhizal symbiosis [2-4]. Furthermore, strigolactones are involved in the regulation of lateral and adventitious root development, root cell division [5, 6], secondary growth [7], and leaf senescence [8]. Recently, we discovered the strigolactone transporter Petunia axillaris PLEIOTROPIC DRUG RESISTANCE 1 (PaPDR1), which is required for efficient mycorrhizal colonization and inhibition of lateral bud outgrowth [9]. However, how strigolactones are transported through the plant remained unknown. Here we show that PaPDR1 exhibits a cell-type-specific asymmetric localization in different root tissues. In root tips, PaPDR1 is co-expressed with the strigolactone biosynthetic gene DAD1 (CCD8), and it is localized at the apical membrane of root hypodermal cells, presumably mediating the shootward transport of strigolactone. Above the root tip, in the hypodermal passage cells that form gates for the entry of mycorrhizal fungi, PaPDR1 is present in the outer-lateral membrane, compatible with its postulated function as strigolactone exporter from root to soil. Transport studies are in line with our localization studies since (1) a papdr1 mutant displays impaired transport of strigolactones out of the root tip to the shoot as well as into the rhizosphere and (2) DAD1 expression and PIN1/PIN2 levels change in plants deregulated for PDR1 expression, suggestive of variations in endogenous strigolactone contents. In conclusion, our results indicate that the polar localizations of PaPDR1 mediate directional shootward strigolactone transport as well as localized exudation into the soil.

A conserved core of programmed cell death indicator genes discriminates developmentally and environmentally induced programmed cell death in plants - Olvera Carrillo, Yadira; Van Bel, Michiel; Van Hautegem, Tom; Fendrych, Matyas; Huysmans, Marlies; Šimášková, Mária; Van Durme, Matthias; Buscaill, Pierre; Rivas, Susana; Coll, Núria; Coppens, Frederik; Maere, Steven; et al. (Plant Physiology)
A plethora of diverse programmed cell death (PCD) processes has been described in living organisms. In animals and plants, different forms of PCD play crucial roles in development, immunity, and responses to the environment. While the molecular control of some animal PCD forms such as apoptosis is known in great detail, we still know comparatively little about the regulation of the diverse types of plant PCD. In part, this deficiency in molecular understanding is caused by the lack of reliable reporters to detect PCD processes. Here, we addressed this issue by using a combination of bioinformatics approaches to identify commonly regulated genes during diverse plant PCD processes in Arabidopsis (Arabidopsis thaliana). Our results indicate that the transcriptional signatures of developmentally controlled cell death are largely distinct from the ones associated with environmentally induced cell death. Moreover, different cases of developmental PCD share a set of cell death-associated genes. Most of these genes are evolutionary conserved within the green plant lineage, arguing for an evolutionary conserved core machinery of developmental PCD. Based on this information, we established an array of specific promoter-reporter lines for developmental PCD in Arabidopsis. These PCD indicators represent a powerful resource that can be used in addition to established morphological and biochemical methods to detect and analyze PCD processes in vivo and in planta.

The Arabidopsis thaliana elongator complex subunit 2 epigenetically affects root development - Jia, Yuebin; Tian, Huiyu; Li, Hongjiang; Yu, Qianqian; Wang, Lei; Friml, Jirí; Ding, Zhaojun (Journal of Experimental Botany)
The elongator complex subunit 2 (ELP2) protein, one subunit of an evolutionarily conserved histone acetyltransferase complex, has been shown to participate in leaf patterning, plant immune and abiotic stress responses in Arabidopsis thaliana. Here, its role in root development was explored. Compared to the wild type, the elp2 mutant exhibited an accelerated differentiation of its root stem cells and cell division was more active in its quiescent centre (QC). The key transcription factors responsible for maintaining root stem cell and QC identity, such as AP2 transcription factors PLT1 (PLETHORA1) and PLT2 (PLETHORA2), GRAS transcription factors such as SCR (SCARECROW) and SHR (SHORT ROOT) and WUSCHEL-RELATED HOMEOBOX5 transcription factor WOX5, were all strongly down-regulated in the mutant. On the other hand, expression of the G2/M transition activator CYCB1 was substantially induced in elp2. The auxin efflux transporters PIN1 and PIN2 showed decreased protein levels and PIN1 also displayed mild polarity alterations in elp2, which resulted in a reduced auxin content in the root tip. Either the acetylation or methylation level of each of these genes differed between the mutant and the wild type, suggesting that the ELP2 regulation of root development involves the epigenetic modification of a range of transcription factors and other developmental regulators.

The cyclophilin a DIAGEOTROPICA gene affects auxin transport in both root and shoot to control lateral root formation - Ivanchenko, Maria; Zhu, Jinsheng; Wang, Bangjun; Medvecka, Eva; Du, Yunlong; Azzarello, Elisa; Mancuso, Stefano; Megraw, Molly; Filichkin, Sergei; Dubrovsky, Joseph; Friml, Jirí; Geisler, Markus (Development)
CyclophilinAis a conserved peptidyl-prolyl cis-trans isomerase (PPIase) best known as the cellular receptor of the immunosuppressant cyclosporine A. Despite significant effort, evidence of developmental functions of cyclophilin A in non-plant systems has remained obscure. Mutations in a tomato (Solanum lycopersicum) cyclophilin A ortholog, DIAGEOTROPICA (DGT), have been shown to abolish the organogenesis of lateral roots; however, a mechanistic explanation of the phenotype is lacking. Here, we show that the dgt mutant lacks auxin maxima relevant to priming and specification of lateral root founder cells. DGT is expressed in shoot and root, and localizes to both the nucleus and cytoplasm during lateral root organogenesis. Mutation of ENTIRE/ IAA9, a member of the auxin-responsive Aux/IAA protein family of transcriptional repressors, partially restores the inability of dgt to initiate lateral root primordia but not the primordia outgrowth. By comparison, grafting of a wild-type scion restores the process of lateral root formation, consistent with participation of a mobile signal. Antibodies do not detect movement of the DGT protein into the dgt rootstock; however, experiments with radiolabeled auxin and an auxin-specific microelectrode demonstrate abnormal auxin fluxes. Functional studies of DGT in heterologous yeast and tobacco-leaf auxin-transport systems demonstrate that DGT negatively regulates PIN-FORMED (PIN) auxin efflux transporters by affecting their plasma membrane localization. Studies in tomato support complex effects of the dgt mutation on PIN expression level, expression domain and plasma membrane localization. Our data demonstrate that DGT regulates auxin transport in lateral root formation.

Reporters for sensitive and quantitative measurement of auxin response - Liao, Cheyang; Smet, Wouter; Brunoud, Géraldine; Yoshida, Saiko; Vernoux, Teva; Weijers, Dolf (Nature Methods)
The visualization of hormonal signaling input and output is key to understanding how multicellular development is regulated. The plant signaling molecule auxin triggers many growth and developmental responses, but current tools lack the sensitivity or precision to visualize these. We developed a set of fluorescent reporters that allow sensitive and semiquantitative readout of auxin responses at cellular resolution in Arabidopsis thaliana. These generic tools are suitable for any transformable plant species.

Auxin-binding pocket of ABP1 is crucial for its gain-of-function cellular and developmental roles - Grones, Peter; Chen, Xu; Simon, Sibu; Kaufmann, Walter; De Rycke, Riet; Nodzyński, Tomasz; Zažímalová, Eva; Friml, Jirí (Journal of Experimental Botany)
The plant hormone auxin is a key regulator of plant growth and development. Auxin levels are sensed and interpreted by distinct receptor systems that activate a broad range of cellular responses. The Auxin-Binding Protein1 (ABP1) that has been identified based on its ability to bind auxin with high affinity is a prime candidate for the extracellular receptor responsible for mediating a range of auxin effects, in particular, the fast non-transcriptional ones. Contradictory genetic studies suggested prominent or no importance of ABP1 in many developmental processes. However, how crucial the role of auxin binding to ABP1 is for its functions has not been addressed. Here, we show that the auxin-binding pocket of ABP1 is essential for its gain-of-function cellular and developmental roles. In total, 16 different abp1 mutants were prepared that possessed substitutions in the metal core or in the hydrophobic amino acids of the auxin-binding pocket as well as neutral mutations. Their analysis revealed that an intact auxin-binding pocket is a prerequisite for ABP1 to activate downstream components of the ABP1 signalling pathway, such as Rho of Plants (ROPs) and to mediate the clathrin association with membranes for endocytosis regulation. In planta analyses demonstrated the importance of the auxin binding pocket for all known ABP1-mediated postembryonic developmental processes, including morphology of leaf epidermal cells, root growth and root meristem activity, and vascular tissue differentiation. Taken together, these findings suggest that auxin binding to ABP1 is central to its function, supporting the role of ABP1 as auxin receptor.

A coherent transcriptional feed-forward motif model for mediating auxin-sensitive PIN3 expression during lateral root development - Chen, Qian; Liu, Yang; Maere, Steven; Lee, Eunkyoung; Van Isterdael, Gert; Xie, Zidian; Xuan, Wei; Lucas, Jessica; Vassileva, Valya; Kitakura, Saeko; Marhavy, Peter; Wabnik, Krzysztof T; et al. (Nature Communications)
Multiple plant developmental processes, such as lateral root development, depend on auxin distribution patterns that are in part generated by the PIN-formed family of auxin-efflux transporters. Here we propose that AUXIN RESPONSE FACTOR7 (ARF7) and the ARF7-regulated FOUR LIPS/MYB124 (FLP) transcription factors jointly form a coherent feed-forward motif that mediates the auxin-responsive PIN3 transcription in planta to steer the early steps of lateral root formation. This regulatory mechanism might endow the PIN3 circuitry with a temporal 'memory' of auxin stimuli, potentially maintaining and enhancing the robustness of the auxin flux directionality during lateral root development. The cooperative action between canonical auxin signalling and other transcription factors might constitute a general mechanism by which transcriptional auxin-sensitivity can be regulated at a tissue-specific level.

An early secretory pathway mediated by gnom-like 1 and gnom is essential for basal polarity establishment in Arabidopsis thaliana - Doyle, Siamsa; Haegera, Ash; Vain, Thomas; Rigala, Adeline; Viotti, Corrado; Łangowskaa, Małgorzata; Maa, Qian; Friml, Jirí; Raikhel, Natasha; Hickse, Glenn; Robert, Stéphanie (PNAS)
Spatial regulation of the plant hormone indole-3-acetic acid (IAA, or auxin) is essential for plant development. Auxin gradient establishment is mediated by polarly localized auxin transporters, including PIN-FORMED (PIN) proteins. Their localization and abundance at the plasma membrane are tightly regulated by endomembrane machinery, especially the endocytic and recycling pathways mediated by the ADP ribosylation factor guanine nucleotide exchange factor (ARF-GEF) GNOM. We assessed the role of the early secretory pathway in establishing PIN1 polarity in Arabidopsis thaliana by pharmacological and genetic approaches. We identified the compound endosidin 8 (ES8), which selectively interferes with PIN1 basal polarity without altering the polarity of apical proteins. ES8 alters the auxin distribution pattern in the root and induces a strong developmental phenotype, including reduced root length. The ARF-GEF- defective mutants gnom-like 1 ( gnl1-1) and gnom ( van7) are significantly resistant to ES8. The compound does not affect recycling or vacuolar trafficking of PIN1 but leads to its intracellular accumulation, resulting in loss of PIN1 basal polarity at the plasma membrane. Our data confirm a role for GNOM in endoplasmic reticulum (ER) - Golgi trafficking and reveal that a GNL1/GNOM-mediated early secretory pathway selectively regulates PIN1 basal polarity establishment in a manner essential for normal plant development.

Cytokinin response factors regulate PIN-FORMED auxin transporters - Šimášková, Mária; O'Brien, José; Khan-Djamei, Mamoona; Van Noorden, Giel; Ötvös, Krisztina; Vieten, Anne; De Clercq, Inge; Van Haperen, Johanna; Cuesta, Candela; Hoyerová, Klára; Vanneste, Steffen; Marhavy, Peter; et al. (Nature Communications)
Auxin and cytokinin are key endogenous regulators of plant development. Although cytokinin-mediated modulation of auxin distribution is a developmentally crucial hormonal interaction, its molecular basis is largely unknown. Here we show a direct regulatory link between cytokinin signalling and the auxin transport machinery uncovering a mechanistic framework for cytokinin-auxin cross-talk. We show that the CYTOKININ RESPONSE FACTORS (CRFs), transcription factors downstream of cytokinin perception, transcriptionally control genes encoding PIN-FORMED (PIN) auxin transporters at a specific PIN CYTOKININ RESPONSE ELEMENT (PCRE) domain. Removal of this cis-regulatory element effectively uncouples PIN transcription from the CRF-mediated cytokinin regulation and attenuates plant cytokinin sensitivity. We propose that CRFs represent a missing cross-talk component that fine-tunes auxin transport capacity downstream of cytokinin signalling to control plant development.

Osmotic stress modulates the balance between exocytosis and clathrin mediated endocytosis in Arabidopsis thaliana - Zwiewka, Marta; Nodzyński, Tomasz; Robert, Stéphanie; Vanneste, Steffen; Friml, Jiřĺ (Molecular Plant)
The sessile life style of plants creates the need to deal with an often adverse environment, in which water availability can change on a daily basis, challenging the cellular physiology and integrity. Changes in osmotic conditions disrupt the equilibrium of the plasma membrane: hypoosmotic conditions increase and hyperosmotic environment decrease the cell volume. Here, we show that short-term extracellular osmotic treatments are closely followed by a shift in the balance between endocytosis and exocytosis in root meristem cells. Acute hyperosmotic treatments (ionic and nonionic) enhance clathrin-mediated endocytosis simultaneously attenuating exocytosis, whereas hypoosmotic treatments have the opposite effects. In addition to clathrin recruitment to the plasma membrane, components of early endocytic trafficking are essential during hyperosmotic stress responses. Consequently, growth of seedlings defective in elements of clathrin or early endocytic machinery is more sensitive to hyperosmotic treatments. We also found that the endocytotic response to a change of osmotic status in the environment is dominant over the presumably evolutionary more recent regulatory effect of plant hormones, such as auxin. These results imply that osmotic perturbation influences the balance between endocytosis and exocytosis acting through clathrin-mediated endocytosis. We propose that tension on the plasma membrane determines the addition or removal of membranes at the cell surface, thus preserving cell integrity.

Calcium is an organizer of cell polarity in plants - Himschoot, Ellie; Beeckman, Tom; Friml, Jiřĺ; Vanneste, Steffen (Biochimica et Biophysica Acta - Molecular Cell Research)
Cell polarity is a fundamental property of pro- and eukaryotic cells. It is necessary for coordination of cell division, cell morphogenesis and signaling processes. How polarity is generated and maintained is a complex issue governed by interconnected feed-back regulations between small GTPase signaling and membrane tension-based signaling that controls membrane trafficking, and cytoskeleton organization and dynamics. Here, we will review the potential role for calcium as a crucial signal that connects and coordinates the respective processes during polarization processes in plants. This article is part of a Special Issue entitled: 13th European Symposium on Calcium.

ABP1: Finally docking - Grones, Peter; Friml, Jiřĺ (Molecular Plant)

Plant embryogenesis requires AUX/LAX-mediated auxin influx - Robert, Hélène; Grunewald, Wim; Sauer, Michael; Cannoot, Bernard; Soriano, Mercedes; Swarup, Ranjan; Weijers, Dolf; Bennett, Malcolm; Boutilier, Kim; Friml, Jirí (Development)
The plant hormone auxin and its directional transport are known to play a crucial role in defining the embryonic axis and subsequent development of the body plan. Although the role of PIN auxin efflux transporters has been clearly assigned during embryonic shoot and root specification, the role of the auxin influx carriers AUX1 and LIKE-AUX1 (LAX) proteins is not well established. Here, we used chemical and genetic tools on Brassica napus microspore-derived embryos and Arabidopsis thaliana zygotic embryos, and demonstrate that AUX1, LAX1 and LAX2 are required for both shoot and root pole formation, in concert with PIN efflux carriers. Furthermore, we uncovered a positive-feedback loop betweenMONOPTEROS(ARF5)-dependent auxin signalling and auxin transport. ThisMONOPTEROSdependent transcriptional regulation of auxin influx (AUX1, LAX1 and LAX2) and auxin efflux (PIN1 and PIN4) carriers by MONOPTEROS helps to maintain proper auxin transport to the root tip. These results indicate that auxin-dependent cell specification during embryo development requires balanced auxin transport involving both influx and efflux mechanisms, and that this transport is maintained by a positive transcriptional feedback on auxin signalling.

Auxin transporters and binding proteins at a glance - Grones, Peter; Friml, Jirí (Journal of Cell Science)
The plant hormone auxin is a key regulator of plant growth and development. Differences in auxin distribution within tissues are mediated by the polar auxin transport machinery, and cellular auxin responses occur depending on changes in cellular auxin levels. Multiple receptor systems at the cell surface and in the interior operate to sense and interpret fluctuations in auxin distribution that occur during plant development. Until now, three proteins or protein complexes that can bind auxin have been identified. SCFTIR1 [a SKP1-cullin-1-F-box complex that contains transport inhibitor response 1 (TIR1) as the F-box protein] and S-phase-kinaseassociated protein 2 (SKP2) localize to the nucleus, whereas auxinbinding protein 1 (ABP1), predominantly associates with the endoplasmic reticulum and cell surface. In this Cell Science at a Glance article, we summarize recent discoveries in the field of auxin transport and signaling that have led to the identification of new components of these pathways, as well as their mutual interaction.

Developing 3D SEM in a broad biological context - Kremer, A; Lippens, Stefaan; Bartunkova, Sonia; Asselbergh, Bob; Blanpain, Cendric; Fendrych, Matyas; Goossens, A; Holt, Matthew; Janssens, Sophie; Krols, Michiel; Larsimont, Jean; Mc Guire, Conor; et al. (Journal of Microscopy)
When electron microscopy (EM) was introduced in the 1930s it gave scientists their first look into the nanoworld of cells. Over the last 80 years EM has vastly increased our understanding of the complex cellular structures that underlie the diverse functions that cells need to maintain life. One drawback that has been difficult to overcome was the inherent lack of volume information, mainly due to the limit on the thickness of sections that could be viewed in a transmission electron microscope (TEM). For many years scientists struggled to achieve three-dimensional (3D) EM using serial section reconstructions, TEM tomography, and scanning EM (SEM) techniques such as freeze-fracture. Although each technique yielded some special information, they required a significant amount of time and specialist expertise to obtain even a very small 3D EM dataset. Almost 20 years ago scientists began to exploit SEMs to image blocks of embedded tissues and perform serial sectioning of these tissues inside the SEM chamber. Using first focused ion beams (FIB) and subsequently robotic ultramicrotomes (serial block-face, SBF-SEM) microscopists were able to collect large volumes of 3D EM information at resolutions that could address many important biological questions, and do so in an efficient manner. We present here some examples of 3D EM taken from the many diverse specimens that have been imaged in our core facility. We propose that the next major step forward will be to efficiently correlate functional information obtained using light microscopy (LM) with 3D EM datasets to more completely investigate the important links between cell structures and their functions.

Phylogenetic relationships of Petrocoptis A. Braun ex Endl. (Caryophyllaceae), a discussed genus from the Iberian Peninsula - Cires Rodriguez, Eduardo; Prieto, José (Journal of Plant Research)
Petrocoptis is a small genus of chasmophytic plants endemic to the Iberian Peninsula, with some localized populations in the French Pyrenees. Within the genus, a dozen species have been recognized based on morphological diversity, most of them with limited distribution area, in small populations and frequently with potential threats to their survival. To date, however, a molecular evaluation of the current systematic treatments has not been carried out. The aim of the present study is to infer phylogenetic relationships among its subordinate taxa by using plastidial rps16 intron and nuclear internal transcribed spacer (ITS) DNA sequences; and evaluate the phylogenetic placement of the genus Petrocoptis within the family Caryophyllaceae. The monophyly of Petrocoptis is supported by both ITS and rps16 intron sequence analyses. Furthermore, time estimates using BEAST analyses indicate a Middle to Late Miocene diversification (10.59 Myr, 6.44–15.26 Myr highest posterior densities [HPD], for ITS; 14.30 Myr, 8.61–21.00 Myr HPD, for rps16 intron).

Intracellular trafficking and PIN-mediated cell polarity during tropic responses in plants - Rakusová, Hana; Fendrych, Matyas; Friml, Jirí (Current Opinion in Plant Biology)

EIN2-directed translational regulation of ethylene signaling in arabidopsis - Li, Wenyang; Ma, Mengdi; Feng, Ying; Li, Hongjiang; Wang, Yichuan; Ma, Yutong; Li, Mingzhe; An, Fengying; Guo, Hongwei (Cell)
Ethylene is a gaseous phytohormone that plays vital roles in plant growth and development. Previous studies uncovered EIN2 as an essential signal transducer linking ethylene perception on ER to transcriptional regulation in the nucleus through a “cleave and shuttle” model. In this study, we report another mechanism of EIN2-mediated ethylene signaling, whereby EIN2 imposes the translational repression of EBF1 and EBF2 mRNA. We find that the EBF1/2 3′ UTRs mediate EIN2-directed translational repression and identify multiple poly-uridylates (PolyU) motifs as functional cis elements of 3′ UTRs. Furthermore, we demonstrate that ethylene induces EIN2 to associate with 3′ UTRs and target EBF1/2 mRNA to cytoplasmic processing-body (P-body) through interacting with multiple P-body factors, including EIN5 and PABs. Our study illustrates translational regulation as a key step in ethylene signaling and presents mRNA 3′ UTR functioning as a “signal transducer” to sense and relay cellular signaling in plants.

PIN-dependent auxin transport: Action, regulation, and evolution - Adamowski, Maciek; Friml, Jirí (Plant Cell)
Auxin participates in a multitude of developmental processes, as well as responses to environmental cues. Compared with other plant hormones, auxin exhibits a unique property, as it undergoes directional, cell-to-cell transport facilitated by plasma membrane-localized transport proteins. Among them, a prominent role has been ascribed to the PIN family of auxin efflux facilitators. PIN proteins direct polar auxin transport on account of their asymmetric subcellular localizations. In this review, we provide an overview of the multiple developmental roles of PIN proteins, including the atypical endoplasmic reticulum-localized members of the family, and look at the family from an evolutionary perspective. Next, we cover the cell biological and molecular aspects of PIN function, in particular the establishment of their polar subcellular localization. Hormonal and environmental inputs into the regulation of PIN action are summarized as well.

Embryo-lethal phenotypes in early abp1 mutants are due to disruption of the neighboring BSM gene - Michalko, Jaroslav; Dravecka, Marta; Bollenbach, Tobias; Friml, Jirí (F1000 Research)
The Auxin Binding Protein1 (ABP1) has been identified based on its ability to bind auxin with high affinity and studied for a long time as a prime candidate for the extracellular auxin receptor responsible for mediating in particular the fast non-transcriptional auxin responses. However, the contradiction between the embryo-lethal phenotypes of the originally described Arabidopsis T-DNA insertional knock-out alleles (abp1-1 and abp1-1s) and the wild type-like phenotypes of other recently described loss-of-function alleles (abp1-c1 and abp1-TD1) questions the biological importance of ABP1 and relevance of the previous genetic studies. Here we show that there is no hidden copy of the ABP1 gene in the Arabidopsis genome but the embryo-lethal phenotypes of abp1-1 and abp1-1s alleles are very similar to the knock-out phenotypes of the neighboring gene, BELAYA SMERT (BSM). Furthermore, the allelic complementation test between bsm and abp1 alleles shows that the embryo-lethality in the abp1-1 and abp1-1s alleles is caused by the off-target disruption of the BSM locus by the T-DNA insertions. This clarifies the controversy of different phenotypes among published abp1 knock-out alleles and asks for reflections on the developmental role of ABP1.

Auxin on the road navigated by cellular PIN polarity - Baster, Pawel; Friml, Jiří (Auxin and Its Role in Plant Development)
The generation of asymmetry, at both cellular and tissue level, is one of the most essential capabilities of all eukaryotic organisms. It mediates basically all multicellular development ranging from embryogenesis and de novo organ formation till responses to various environmental stimuli. In plants, the awe-inspiring number of such processes is regulated by phytohormone auxin and its directional, cell-to-cell transport. The mediators of this transport, PIN auxin transporters, are asymmetrically localized at the plasma membrane, and this polar localization determines the directionality of intercellular auxin flow. Thus, auxin transport contributes crucially to the generation of local auxin gradients or maxima, which instruct given cell to change its developmental program. Here, we introduce and discuss the molecular components and cellular mechanisms regulating the generation and maintenance of cellular PIN polarity, as the general hallmarks of cell polarity in plants.

An auxin-mediated shift toward growth isotropy promotes organ formation at the shoot meristem in Arabidopsis - Sassi, Massimiliano; Ali, Olivier; Boudon, Frédéric; Cloarec, Gladys; Abad, Ursula; Cellier, Coralie; Chen, Xu; Gilles, Benjamin; Milani, Pascale; Friml, Jirí; Vernoux, Teva; Godin, Christophe; et al. (Current Biology)
To control morphogenesis, molecular regulatory networks have to interfere with the mechanical properties of the individual cells of developing organs and tissues, but how this is achieved is not well known. We study this issue here in the shoot meristem of higher plants, a group of undifferentiated cells where complex changes in growth rates and directions lead to the continuous formation of new organs [1, 2]. Here, we show that the plant hormone auxin plays an important role in this process via a dual, local effect on the extracellular matrix, the cell wall, which determines cell shape. Our study reveals that auxin not only causes a limited reduction in wall stiffness but also directly interferes with wall anisotropy via the regulation of cortical microtubule dynamics. We further show that to induce growth isotropy and organ outgrowth, auxin somehow interferes with the cortical microtubule-ordering activity of a network of proteins, including AUXIN BINDING PROTEIN 1 and KATANIN 1. Numerical simulations further indicate that the induced isotropy is sufficient to amplify the effects of the relatively minor changes in wall stiffness to promote organogenesis and the establishment of new growth axes in a robust manner.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

SAC phosphoinositide phosphatases at the tonoplast mediate vacuolar function in Arabidopsis - Nováková, Petra; Hirsch, Sibylle; Feraru, Elena; Tejos, Ricardo; Van Wijk, Ringo; Viaene, Tom; Heilmann, Mareike; Lerche, Jennifer; De Rycke, Riet; Feraru, Mugurel; Grones, Peter; Van Montagu, Marc; et al. (PNAS)
Phosphatidylinositol (PtdIns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, PtdIns3P and PtdIns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vacuolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with PtdIns3P, the presumable product of their activity. In SAC gain- and loss-of-function mutants, the levels of PtdIns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with PtdIns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Insights into the localization and function of the membrane trafficking regulator GNOM ARF-GEF at the Golgi apparatus in Arabidopsis - Naramoto, Satoshi; Otegui, Marisa; Kutsuna, Natsumaro; De Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jirí (Plant Cell)
GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana. State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans-Golgi network (TGN)/early endosomes (EEs). Malformed TGN/EE in gnom mutants suggests a role for GNOM in maintaining TGN/EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.

WOX5-IAA17 feedback circuit-mediated cellular auxin response is crucial for the patterning of root stem cell niches in arabidopsis - Tian, Huiyu; Wabnik, Krzysztof T; Niu, Tiantian; Li, Hongjiang; Yu, Qianqian; Pollmann, Stephan; Vanneste, Steffen; Govaerts, Willy; Rolčík, Jakub; Geisler, Markus; Friml, Jirí; Ding, Zhaojun (Molecular Plant)
In plants, the patterning of stem cell-enriched meristems requires a graded auxin response maximum that emerges from the concerted action of polar auxin transport, auxin biosynthesis, auxin metabolism, and cellular auxin response machinery. However, mechanisms underlying this auxin response maximum-mediated root stem cell maintenance are not fully understood. Here, we present unexpected evidence that WUSCHEL-RELATED HOMEOBOX 5 (WOX5) transcription factor modulates expression of auxin biosynthetic genes in the quiescent center (QC) of the root and thus provides a robust mechanism for the maintenance of auxin response maximum in the root tip. This WOX5 action is balanced through the activity of indole-3-acetic acid 17 (IAA17) auxin response repressor. Our combined genetic, cell biology, and computational modeling studies revealed a previously uncharacterized feedback loop linking WOX5-mediated auxin production to IAA17-dependent repression of auxin responses. This WOX5-IAA17 feedback circuit further assures the maintenance of auxin response maximum in the root tip and thereby contributes to the maintenance of distal stem cell (DSC) populations. Our experimental studies and in silico computer simulations both demonstrate that the WOX5-IAA17 feedback circuit is essential for the maintenance of auxin gradient in the root tip and the auxin-mediated root DSC differentiation.

Cell surface ABP1-TMK auxin sensing complex activates ROP GTPase signaling - Xu, Tongda; Dai, Ning; Chen, Jisheng; Nagawa, Shingo; Cao, Min; Li, Hongjiang; Zhou, Zimin; Chen, Xu; De Rycke, Riet; Rakusová, Hana; Wang, Wen; Jones, Alan; et al. (Science)
Auxin-binding protein 1 (ABP1) was discovered nearly 40 years ago and was shown to be essential for plant development and morphogenesis, but its mode of action remains unclear. Here, we report that the plasma membrane-localized transmembrane kinase (TMK) receptor-like kinases interact with ABP1 and transduce auxin signal to activate plasma membrane-associated ROPs [Rho-like guanosine triphosphatases (GTPase) from plants], leading to changes in the cytoskeleton and the shape of leaf pavement cells in Arabidopsis. The interaction between ABP1 and TMK at the cell surface is induced by auxin and requires ABP1 sensing of auxin. These findings show that TMK proteins and ABP1 form a cell surface auxin perception complex that activates ROP signaling pathways, regulating nontranscriptional cytoplasmic responses and associated fundamental processes.

Rho-GTPase-regulated vesicle trafficking in plant cell polarity - Chen, Xu; Friml, Jirí (Biochemical Society Transactions)
ROPs (Rho of plants) belong to a large family of plant-specific Rho-like small GTPases that function as essential molecular switches to control diverse cellular processes including cytoskeleton organization, cell polarization, cytokinesis, cell differentiation and vesicle trafficking. Although the machineries of vesicle trafficking and cell polarity in plants have been individually well addressed, how ROPs co-ordinate those processes is still largely unclear. Recent progress has been made towards an understanding of the coordination of ROP signalling and trafficking of PIN (PINFORMED) transporters for the plant hormone auxin in both root and leaf pavement cells. PIN transporters constantly shuttle between the endosomal compartments and the polar plasma membrane domains, therefore the modulation of PIN-dependent auxin transport between cells is a main developmental output of ROP-regulated vesicle trafficking. The present review focuses on these cellular mechanisms, especially the integration of ROP-based vesicle trafficking and plant cell polarity.

Plant biology: Gatekeepers of the road to protein perdition - Sauer, Michael; Friml, Jirí (Current Biology)
Targeting membrane proteins for degradation requires the sequential action of ESCRT sub-complexes ESCRT-0 to ESCRT-III. Although this machinery is generally conserved among kingdoms, plants lack the essential ESCRT-0 components. A new report closes this gap by identifying a novel protein family that substitutes for ESCRT-0 function in plants.

Bipolar plasma membrane distribution of phosphoinositides and their requirement for auxin-mediated cell polarity and patterning in Arabidopsis - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, MiriamPalacios; Li, Hongjiang; Heilmann, Mareike; Van Wijk, Ringo; Vermeer, Joop; Heilmann, Ingo; Munnik, Teun; Friml, Jirí (Plant Cell)
Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM. Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain-delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.

Auxin transport and activity regulate stomatal patterning and development - Le, Jie; Liu, Xuguang; Yang, Kezhen; Chen, Xiaolan; Zhu, Lingling; Wang, Hongzhe; Wang, Ming; Vanneste, Steffen; Morita, Miyo; Tasaka, Masao; Ding, Zhaojun; Friml, Jirí; et al. (Nature Communications)
Stomata are two-celled valves that control epidermal pores whose spacing optimizes shoot-atmosphere gas exchange. They develop from protodermal cells after unequal divisions followed by an equal division and differentiation. The concentration of the hormone auxin, a master plant developmental regulator, is tightly controlled in time and space, but its role, if any, in stomatal formation is obscure. Here dynamic changes of auxin activity during stomatal development are monitored using auxin input (DII-VENUS) and output (DR5:VENUS) markers by time-lapse imaging. A decrease in auxin levels in the smaller daughter cell after unequal division presages the acquisition of a guard mother cell fate whose equal division produces the two guard cells. Thus, stomatal patterning requires auxin pathway control of stem cell compartment size, as well as auxin depletion that triggers a developmental switch from unequal to equal division.

Cytokinin controls polarity of PIN1-dependent Auxin transport during lateral root organogenesis - Marhavy, Peter; Duclercq, Jérôme; Weller, Benjamin; Feraru, Elena; Bielach, Agnieszka; Offringa, Remko; Friml, Jirí; Schwechheimer, Claus; Murphy, Angus; Benková, Eva (Current Biology)
The plant hormones auxin and cytokinin mutually coordinate their activities to control various aspects of development [1-9], and their crosstalk occurs at multiple levels [10, 11]. Cytokinin-mediated modulation of auxin transport provides an efficient means to regulate auxin distribution in plant organs. Here, we demonstrate that cytokinin does not merely control the overall auxin flow capacity, but might also act as a polarizing cue and control the auxin stream directionality during plant organogenesis. Cytokinin enhances the PIN-FORMED1 (PIN1) auxin transporter depletion at specific polar domains, thus rearranging the cellular PIN polarities and directly regulating the auxin flow direction. This selective cytokinin sensitivity correlates with the PIN protein phosphorylation degree. PIN1 phosphomimicking mutations, as well as enhanced phosphorylation in plants with modulated activities of PIN-specific kinases and phosphatases, desensitize PIN1 to cytokinin. Our results reveal conceptually novel, cytokinin-driven polarization mechanism that operates in developmental processes involving rapid auxin stream redirection, such as lateral root organogenesis, in which a gradual PIN polarity switch defines the growth axis of the newly formed organ.

Bimodal regulation of ICR1 levels generates self-organizing auxin distribution - Hazak, Ora; Obolski, Uri; Prat, Tomas; Friml, Jiří; Hadany, Lilach; Yalovsky, Shaul (PNAS)
Auxin polar transport, local maxima, and gradients have become an importantmodel system for studying self-organization. Auxin distribution is regulated by auxin-dependent positive feedback loops that are not well-understood at the molecular level. Previously, we showed the involvement of the RHO of Plants (ROP) effector INTERACTOR of CONSTITUTIVELY active ROP 1 (ICR1) in regulation of auxin transport and that ICR1 levels are posttranscriptionally repressed at the site of maximum auxin accumulation at the root tip. Here, we show that bimodal regulation of ICR1 levels by auxin is essential for regulating formation of auxin local maxima and gradients. ICR1 levels increase concomitant with increase in auxin response in lateral root primordia, cotyledon tips, and provascular tissues. However, in the embryo hypophysis and root meristem, when auxin exceeds critical levels, ICR1 is rapidly destabilized by an SCF(TIR1/AFB) [SKP, Cullin, F-box (transport inhibitor response 1/auxin signaling F-box protein)]-dependent auxin signaling mechanism. Furthermore, ectopic expression of ICR1 in the embryo hypophysis resulted in reduction of auxin accumulation and concomitant root growth arrest. ICR1 disappeared during root regeneration and lateral root initiation concomitantly with the formation of a local auxin maximum in response to external auxin treatments and transiently after gravitropic stimulation. Destabilization of ICR1 was impaired after inhibition of auxin transport and signaling, proteasome function, and protein synthesis. A mathematical model based on these findings shows that an in vivo-like auxin distribution, rootward auxin flux, and shootward reflux can be simulated without assuming preexisting tissue polarity. Our experimental results and mathematical modeling indicate that regulation of auxin distribution is tightly associated with auxin-dependent ICR1 levels.

Directional auxin transport mechanisms in early diverging land plants - Viaene, Tom; Landberg, Katarina; Thelander, Mattias; Medvecka, Eva; Pederson, Eric; Feraru, Elena; Cooper, Endymion; Karimi, Mansour; Delwiche, Charles; Ljung, Karin; Geisler, Markus; Sundberg, Eva; et al. (Current Biology)
The emergence and radiation of multicellular land plants was driven by crucial innovations to their body plans [1]. The directional transport of the phytohormone auxin represents a key, plant-specific mechanism for polarization and patterning in complex seed plants [2-5]. Here, we show that already in the early diverging land plant lineage, as exemplified by the moss Physcomitrella patens, auxin transport by PIN transporters is operational and diversified into ER-localized and plasma membrane-localized PIN proteins. Gain-of-function and loss-of-function analyses revealed that PIN-dependent intercellular auxin transport in Physcomitrella mediates crucial developmental transitions in tip-growing filaments and waves of polarization and differentiation in leaf-like structures. Plasma membrane PIN proteins localize in a polar manner to the tips of moss filaments, revealing an unexpected relation between polarization mechanisms in moss tip-growing cells and multicellular tissues of seed plants. Our results trace the origins of polarization and auxin-mediated patterning mechanisms and highlight the crucial role of polarized auxin transport during the evolution of multicellular land plants.

Cellular events during interfascicular cambium ontogenesis in inflorescence stems of Arabidopsis - Mazur, Ewa; Kurczyñska, Ewa; Friml, Jiří (Protoplasma)
Development of cambium and its activity is important for our knowledge of the mechanism of secondary growth. Arabidopsis thaliana emerges as a good model plant for such a kind of study. Thus, this paper reports on cellular events taking place in the interfascicular regions of inflorescence stems of A. thaliana, leading to the development of interfascicular cambium from differentiated interfascicular parenchyma cells (IPC). These events are as follows: appearance of auxin accumulation, PIN1 gene expression, polar PIN1 protein localization in the basal plasma membrane and periclinal divisions. Distribution of auxin was observed to be higher in differentiating into cambium parenchyma cells compared to cells within the pith and cortex. Expression of PIN1 in IPC was always preceded by auxin accumulation. Basal localization of PIN1 was already established in the cells prior to their periclinal division. These cellular events initiated within parenchyma cells adjacent to the vascular bundles and successively extended from that point towards the middle region of the interfascicular area, located between neighboring vascular bundles. The final consequence of which was the closure of the cambial ring within the stem. Changes in the chemical composition of IPC walls were also detected and included changes of pectic epitopes, xyloglucans (XG) and extensins rich in hydroxyproline (HRGPs). In summary, results presented in this paper describe interfascicular cambium ontogenesis in terms of successive cellular events in the interfascicular regions of inflorescence stems of Arabidopsis.

Polar delivery in plants; commonalities and differences to animal epithelial cells - Kania, Urszula; Fendrych, Matyas; Friml, Jiřĺ (Open Biology)
Although plant and animal cells use a similar core mechanism to deliver proteins to the plasma membrane, their different lifestyle, body organization and specific cell structures resulted in the acquisition of regulatory mechanisms that vary in the two kingdoms. In particular, cell polarity regulators do not seem to be conserved, because genes encoding key components are absent in plant genomes. In plants, the broad knowledge on polarity derives from the study of auxin transporters, the PIN-FORMED proteins, in the model plant Arabidopsis thaliana. In animals, much information is provided from the study of polarity in epithelial cells that exhibit basolateral and luminal apical polarities, separated by tight junctions. In this review, we summarize the similarities and differences of the polarization mechanisms between plants and animals and survey the main genetic approaches that have been used to characterize new genes involved in polarity establishment in plants, including the frequently used forward and reverse genetics screens as well as a novel chemical genetics approach that is expected to overcome the limitation of classical genetics methods.

BEX1/ARF1A1C is required for BFA-sensitive recycling of PIN auxin transporters and auxin-mediated development in arabidopsis - Tanaka, Hirokazu; Nodzyński, Tomasz; Kitakura, Saeko; Feraru, Mugurel; Sasabe, Michiko; Ishikawa, Tomomi; Kleine Vehn, Jürgen; Kakimoto, Tatsuo; Friml, Jirí (Plant and Cell Physiology)
Correct positioning of membrane proteins is an essential process in eukaryotic organisms. The plant hormone auxin is distributed through intercellular transport and triggers various cellular responses. Auxin transporters of the PIN-FORMED (PIN) family localize asymmetrically at the plasma membrane (PM) and mediate the directional transport of auxin between cells. A fungal toxin, brefeldin A (BFA), inhibits a subset of guanine nucleotide exchange factors for ADP-ribosylation factor small GTPases (ARF GEFs) including GNOM, which plays a major role in localization of PIN1 predominantly to the basal side of the PM. The Arabidopsis genome encodes 19 ARF-related putative GTPases. However, ARF components involved in PIN1 localization have been genetically poorly defined. Using a fluorescence imaging-based forward genetic approach, we identified an Arabidopsis mutant, bfa-visualized exocytic trafficking defective1 (bex1), in which PM localization of PIN1-green fluorescent protein (GFP) as well as development is hypersensitive to BFA. We found that in bex1 a member of the ARF1 gene family, ARF1A1C, was mutated. ARF1A1C localizes to the trans-Golgi network/early endosome and Golgi apparatus, acts synergistically to BEN1/MIN7 ARF GEF and is important for PIN recycling to the PM. Consistent with the developmental importance of PIN proteins, functional interference with ARF1 resulted in an impaired auxin response gradient and various developmental defects including embryonic patterning defects and growth arrest. Our results show that ARF1A1C is essential for recycling of PIN auxin transporters and for various auxin-dependent developmental processes.

VAN4 encodes a putative TRS120 that is required for normal cell growth and vein development in arabidopsis - Naramoto, Satoshi; Nodzyński, Tomasz; Dainobu, Tomoko; Takatsuka, Hirotomo; Okada, Teruyo; Friml, Jirí; Fukuda, Hiroo (Plant and Cell Physiology)
Leaf venation develops complex patterns in angiosperms, but the mechanism underlying this process is largely unknown. To elucidate the molecular mechanisms governing vein pattern formation, we previously isolated vascular network defective (van) mutants that displayed venation discontinuities. Here, we report the phenotypic analysis of van4 mutants, and we identify and characterize the VAN4 gene. Detailed phenotypic analysis shows that van4 mutants are defective in procambium cell differentiation and subsequent vascular cell differentiation. Reduced shoot and root cell growth is observed in van4 mutants, suggesting that VAN4 function is important for cell growth and the establishment of venation continuity. Consistent with these phenotypes, the VAN4 gene is strongly expressed in vascular and meristematic cells. VAN4 encodes a putative TRS120, which is a known guanine nucleotide exchange factor (GEF) for Rab GTPase involved in regulating vesicle transport, and a known tethering factor that determines the specificity of membrane fusion. VAN4 protein localizes at the trans-Golgi network/early endosome (TGN/EE). Aberrant recycling of the auxin efflux carrier PIN proteins is observed in van4 mutants. These results suggest that VAN4-mediated exocytosis at the TGN plays important roles in plant vascular development and cell growth in shoot and root. Our identification of VAN4 as a putative TRS120 shows that Rab GTPases are crucial (in addition to ARF GTPases) for continuous vascular development, and provides further evidence for the importance of vesicle transport in leaf vascular formation.

Allopolyploid origin of the Balkan endemic Ranunculus wettsteinii (Ranunculaceae) inferred from nuclear and plastid DNA sequences - Cires Rodriguez, Eduardo; Baltisberger, Matthias; Cuesta, Candela; Vargas, Pablo; Prieto, José (Organisms Diversity and Evolution)
The Balkan Peninsula, characterized by high rates of endemism, is recognised as one of the most diverse and species-rich areas of Europe. However, little is known about the origin of Balkan endemics. The present study addresses the phylogenetic position of the Balkan endemic Ranunculus wettsteinii, as well as its taxonomic status and relationship with the widespread R. parnassiifolius, based on nuclear DNA (internal transcribed spacer, ITS) and plastid regions (rpl32-trnL, rps16-trnQ, trnK-matK and ycf6-psbM). Maximum parsimony and Bayesian inference analyses revealed a well-supported clade formed by accessions of R. wettsteinii. Furthermore, our phylogenetic and network analyses supported previous hypotheses of a likely allopolyploid origin for R. wettsteinii between R. montenegrinus and R. parnassiifolius, with the latter as the maternal parent.

The TPLATE adaptor complex drives clathrin-mediated endocytosis in plants - Gadeyne, Astrid; Sánchez Rodríguez, Clara; Vanneste, Steffen; Di Rubbo, Simone; Zauber, Henrik; Vanneste, Kevin; Van Leene, Jelle; De Winne, Nancy; Eeckhout, Dominique; Persiau, Geert; Van De Slijke, Eveline; Cannoot, Bernard; et al. (Cell)
Clathrin-mediated endocytosis is the major mechanism for eukaryotic plasma membrane-based proteome turn-over. In plants, clathrin-mediated endocytosis is essential for physiology and development, but the identification and organization of the machinery operating this process remains largely obscure. Here, we identified an eight-core-component protein complex, the TPLATE complex, essential for plant growth via its role as major adaptor module for clathrin-mediated endocytosis. This complex consists of evolutionarily unique proteins that associate closely with core endocytic elements. The TPLATE complex is recruited as dynamic foci at the plasma membrane preceding recruitment of adaptor protein complex 2, clathrin, and dynamin-related proteins. Reduced function of different complex components severely impaired internalization of assorted endocytic cargoes, demonstrating its pivotal role in clathrin-mediated endocytosis. Taken together, the TPLATE complex is an early endocytic module representing a unique evolutionary plant adaptation of the canonical eukaryotic pathway for clathrin-mediated endocytosis.

Analyzing the in vivo status of exogenously applied auxins: A HPLC-based method to characterize the intracellularly localized auxin transporters - Simon, Sibu; Skůpa, Petr; Dobrev, Petre; Petrášek, Jan; Zažímalová, Eva; Friml, Jirí (Plant Chemical Genomics)
Exogenous application of biologically important molecules for plant growth promotion and/or regulation is very common both in plant research and horticulture. Plant hormones such as auxins and cytokinins are classes of compounds which are often applied exogenously. Nevertheless, plants possess a well-established machinery to regulate the active pool of exogenously applied compounds by converting them to metabolites and conjugates. Consequently, it is often very useful to know the in vivo status of applied compounds to connect them with some of the regulatory events in plant developmental processes. The in vivo status of applied compounds can be measured by incubating plants with radiolabeled compounds, followed by extraction, purification, and HPLC metabolic profiling of plant extracts. Recently we have used this method to characterize the intracellularly localized PIN protein, PIN5. Here we explain the method in detail, with a focus on general application.